Sulfur-containing polymer, its production method, and sulfur-containing polymer composition
Patent Information
- Application Number
- JP2022552041
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-03-18
- Filing Date
- 2021-09-22
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2041-09-22
AI Technical Summary
【0022】 本発明によれば、高屈折率で硫黄含有重合体、及び、硫黄含有重合体組成物を提供することができる。本発明の硫黄含有重合体、及び、硫黄含有重合体組成物は、撮像系レンズ材料等の光学用途に好適に使用することができる。
Smart Images

Figure 0007641977000039 
Figure 0007641977000040 
Figure 0007641977000041
Abstract
Description
[Technical field]
[0001] The present invention relates to a sulfur-containing polymer, a method for producing the same, and a sulfur-containing polymer composition. More specifically, the present invention relates to a sulfur-containing polymer having a high refractive index, a method for producing the same, and a sulfur-containing polymer composition. [Background technology]
[0002] Polycarbonate with aromatic rings and polymeric materials with fluorene skeletons are known as high refractive index materials. Refractive index adjustment materials that improve the light extraction efficiency of LEDs and lens materials for imaging systems require materials with large Abbe numbers, i.e., small light dispersion. Materials with sulfur or halogen molecules and materials containing metal oxide nanoparticles have been developed as such materials with high refractive index and small light dispersion.
[0003] Various sulfur-containing materials with high refractive index and small light dispersion have been studied. For example, Patent Document 1 describes a polymer material that has a repeating unit containing a benzene ring in which two hydrogen atoms are substituted with methyl groups and a sulfur atom in the main chain, and has a polydispersity of 3.0 or more, and thus has excellent moldability in a solution state. Furthermore, for example, Patent Document 2 describes a polymer material that contains a polymer having a repeating unit containing a benzene ring in which one hydrogen atom is substituted with a methyl group and a sulfur atom in the main chain, and thus has excellent moldability in a solution state and can be used to form an optical component having a high refractive index. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2015-168790 A [Patent Document 2] JP 2017-52834 A Summary of the Invention [Problem to be solved by the invention]
[0005] However, the refractive index of the above-mentioned polymeric materials is still not sufficiently high, and there is room for improvement. In recent years, there has been a demand for polymeric materials that have a high refractive index and can be imparted with excellent physical properties required for various applications such as optical applications, such as heat resistance, mechanical strength, and adhesion to substrates, and that can be used in a wider range of applications.
[0006] In view of the above-mentioned current situation, an object of the present invention is to provide a polymer material which has a high refractive index and can be suitably used for optical applications and the like. [Means for solving the problem]
[0007] The present inventors have conducted various studies on high refractive index materials and have found that a sulfur-containing polymer having a specific functional group and a specific structure can be a polymer material having a high refractive index and suitable for use in optical applications, etc. Furthermore, they have found that a sulfur-containing polymer composition made by combining such a sulfur-containing polymer with an inorganic substance can be a high refractive index material having excellent transparency and suitable for use as an optical material, etc., and have completed the present invention.
[0008] That is, the present invention relates to a polymer having at least one structural unit selected from the group consisting of a structural unit (A) represented by the following general formula (1), a structural unit (B) represented by the following general formula (2), and a structural unit (C) represented by the following general formula (3), wherein the polymer is a sulfur-containing polymer having a reactive functional group.
[0009] [ka]
[0010] [ka]
[0011] [ka]
[0012] (In the formulas (1), (2) and (3), X 1 , X 2 and X 3 are the same or different and each represents a divalent aromatic hydrocarbon group which may have a substituent.
[0013] The above sulfur-containing polymer preferably contains, as a repeating unit, at least one type of structural unit selected from the group consisting of the above structural unit (A), structural unit (B), and structural unit (C).
[0014] The sulfur-containing polymer preferably has the reactive functional group at the main chain end and / or at a side chain.
[0015] In the sulfur-containing polymer, the reactive functional group is preferably at least one functional group selected from the group consisting of a carboxyl group, a phosphoric acid group, a phosphonic acid group, a hydroxyl group, and a curable functional group, or a group containing such a functional group.
[0016] In the sulfur-containing polymer, the substituent is preferably a reactive functional group, a halogen atom, or an alkyl group, an alkoxy group, an aryl group, an aralkyl group, or a sulfur-containing substituent, which may have a substituent.
[0017] In the sulfur-containing polymer, the element content ratio (O / S) of oxygen atoms O bonded to sulfur atoms S in the main chain to sulfur atoms S in the main chain is preferably 0.1 to 1.5.
[0018] The sulfur-containing polymer is preferably for optical use.
[0019] The present invention also relates to a sulfur-containing polymer composition comprising the above-mentioned sulfur-containing polymer and at least one selected from the group consisting of an inorganic substance, a crosslinking agent, and an organic resin.
[0020] The present invention also relates to a cured product of the above-mentioned sulfur-containing polymer. The present invention also relates to a cured product of the above-mentioned sulfur-containing polymer composition.
[0021] The present invention also relates to a method for producing the above-mentioned sulfur-containing polymer, which is characterized by comprising a step of reacting a sulfur-containing aromatic polymer having a terminal disulfide bond and / or a thiol group with a compound having a polymerizable double bond and a reactive functional group. Effect of the Invention
[0022] According to the present invention, it is possible to provide a sulfur-containing polymer and a sulfur-containing polymer composition having a high refractive index. The sulfur-containing polymer and the sulfur-containing polymer composition of the present invention can be suitably used for optical applications such as imaging lens materials. [Brief description of the drawings]
[0023] [Figure 1] 1 is a photograph of the hybrid membrane obtained in Example 1. [Diagram 2] 1 is a photograph of the nanoparticle dispersions of Example 2 and Comparative Example 1. [Diagram 3] 1 is a photograph of a hybrid membrane obtained using the nanoparticle dispersions of Example 2 and Comparative Example 1. [Figure 4] 1 is a photograph of the hybrid membranes obtained in Experimental Examples 3-1, 3-4, and 3-5. [Diagram 5] FIG. 13 is a diagram showing measurement data of refractive indexes of hybrid solutions of Experimental Examples 8-1 and 8-4 in Example 7. [Figure 6] 1 shows photographs of the hybrid membranes obtained in Experimental Examples 8-1 to 8-4 in Example 7. [Figure 7] FIG. 1 shows XRD profiles of PPS and P1 in Example 9. [Figure 8] FIG. 13 shows measurement data of the transmittance of the P1 film of Example 9. [Figure 9] FIG. 13 shows the measurement data of the refractive index of the P1 film of Example 9. [Figure 10] FIG. 1 shows XRD profiles of PPS and P2 in Example 9. [Figure 11] FIG. 1 shows DSC curves of P1 and P2. [Figure 12] FIG. 13 shows measurement data of the transmittance of the P2 film of Example 9. [Figure 13] FIG. 13 shows measurement data of the refractive index of the P2 film in Example 9. [Figure 14] FIG. 1 shows measurement data of transmittance of OHPPS and Me-OMePPS. [Figure 15] FIG. 1 shows measurement data of the refractive indexes of OHPPS and Me-OMePPS. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0024] The present invention will be described in detail below. In addition, a combination of two or more of the individual preferred embodiments of the present invention described below is also a preferred embodiment of the present invention.
[0025] 1. Sulfur-containing polymer The sulfur-containing polymer of the present invention is a polymer having at least one structural unit selected from the group consisting of a structural unit (A) represented by the following general formula (1), a structural unit (B) represented by the following general formula (2), and a structural unit (C) represented by the following general formula (3), and the polymer is characterized in having a reactive functional group.
[0026] [ka]
[0027] [ka]
[0028] [ka]
[0029] (In the formulas (1), (2) and (3), X 1 , X 2 and X 3 are the same or different and each represents a divalent aromatic hydrocarbon group which may have a substituent. The sulfur-containing polymer of the present invention has a high refractive index because of the above-mentioned composition. It is presumed that the sulfur-containing polymer of the present invention has a high refractive index because it contains a structural unit in which an S atom, which has a high atomic refraction, is directly bonded to an aromatic hydrocarbon group.
[0030] The sulfur-containing polymer of the present invention is characterized by having a reactive functional group. The reactive functional group can be appropriately selected depending on the purpose and application of the sulfur-containing polymer of the present invention, and examples thereof include acidic functional groups such as a carboxyl group (-COOH), a phosphoric acid group (-OPO(OH)3), a hydroxyl group (-OH), a sulfo group (-SO3H), a sulfate group (-OSO3H), a phosphonic acid group (-PO(OH)3), a phosphinic acid group (-PO(OH)-), and a thiol group (mercapto group) (-SH); an amino group, an ammonium group, an imino group, an amide group, an imide group, a maleimide group, and a cyano group. Examples of such functional groups include basic functional groups; curable functional groups such as groups having a reactive unsaturated bond (for example, a group having a reactive double bond, typical examples of which include a vinyl group, a (meth)acryloyl group, an allyl group, and a methallyl group) and groups having a reactive ionic bond (for example, a group having a reactive cyclic ether group, a group having a reactive cyclic thioether, typical examples of which include an epoxy group, an oxetane group, and an episulfide (thiirane)); a nitro group; a nitroso group; and groups containing these functional groups. Examples of the groups containing these functional groups include the above-mentioned acidic functional group, basic functional group, curable functional group, nitro group, or nitroso group, and a group having a hydrocarbon chain or a bonding group. That is, in the present invention, the reactive functional group includes not only the above-mentioned acidic functional group, basic functional group, curable functional group, nitro group and nitroso group, but also groups containing these functional groups and a binding chain. Examples of the linking chain include divalent hydrocarbon groups such as alkylene groups and arylene groups, linking groups such as ether, ester, carbonyl, and amide, and combinations of these.
[0031] Among the above reactive functional groups, for example, from the viewpoint of improving the dispersibility of inorganic substances, acidic functional groups, basic functional groups, or groups containing these functional groups are preferred, and carboxyl groups, phosphoric acid groups, phosphonic acid groups, hydroxyl groups, or groups containing these functional groups are more preferred. From the viewpoint of a low linear expansion coefficient, a carboxyl group, a phosphoric acid group, a phosphonic acid group, a hydroxyl group, or a group containing these functional groups is preferred, and a hydroxyl group or a group containing a hydroxyl group is more preferred. From the viewpoint of improving adhesion to the substrate, a carboxyl group, a phosphoric acid group, a phosphonic acid group, or a group containing these functional groups is preferred, and a phosphoric acid group, a phosphonic acid group, or a group containing these functional groups is more preferred. From the viewpoint of improving heat resistance, mechanical strength, and solvent resistance, a carboxyl group, a hydroxyl group, an amino group, a maleimide group, a curable functional group, or a group containing these functional groups is preferred, and a carboxyl group, a hydroxyl group, an amino group, a maleimide group, a vinyl group, a (meth)acryloyl group, an allyl group, a methallyl group, an epoxy group, an oxetane group, or a group containing these functional groups is more preferred.
[0032] Among these, in terms of being able to impart a higher refractive index along with excellent physical properties, the reactive functional group is preferably a carboxyl group, a phosphate group, a phosphonic acid group, a hydroxyl group, a curable functional group, or a group containing these functional groups, more preferably a carboxyl group, a phosphate group, a hydroxyl group, a vinyl group, an epoxy group, or a group containing these functional groups, and even more preferably a phosphate group, a hydroxyl group, a vinyl group, or a group containing these functional groups. In addition to the high refractive index, the reactive functional group is more preferably a carboxyl group, a phosphate group, or a group containing these functional groups, in that it has a low linear expansion coefficient and can improve adhesion to the substrate.
[0033] The sulfur-containing polymer also preferably has a substituent involved in hydrogen bonding among the reactive functional groups, in that the refractive index can be increased by the hydrogen bonding, which increases the density of the polymer and increases the refractive index. Examples of the substituent participating in the hydrogen bond include a hydroxyl group, a carboxylic acid group, an amino group, an amido group, an imido group, a cyano group, a nitro group, a nitroso group, and a sulfonic acid group. The amount of the substituents participating in the hydrogen bonds is preferably 10 mol % or more per repeating unit (monomer constituent unit) of the sulfur-containing polymer, more preferably 20 mol % or more, even more preferably 50 mol % or more, even more preferably 70 mol % or more, and particularly preferably 90 mol % or more. One repeating unit may contain two or more kinds of the substituents participating in the hydrogen bond, and the amount is preferably 0.1 moles or more on average, more preferably 0.5 moles or more, even more preferably 1 mole or more, even more preferably 1.5 moles or more, even more preferably 2 moles or more, and particularly preferably 3 moles or more. From the viewpoints of solubility in a solvent and heat resistance, the amount of the substituents participating in the hydrogen bond is preferably less than 4 moles on average, more preferably less than 3.5 moles.
[0034] The sulfur-containing polymer may have one or more of the reactive functional groups described above.
[0035] The sulfur-containing polymer preferably has the reactive functional group at the main chain end and / or the side chain. By having the reactive functional group at least at the main chain end or the side chain, the sulfur-containing polymer can exhibit excellent physical properties due to the reactive functional group in addition to a high refractive index. The case where the reactive functional group is present in a side chain includes not only the case where the reactive functional group is present in the side chain of the sulfur-containing polymer, but also the case where the substituent in the structural units (A) to (C) represented by the general formulas (1) to (3) is the reactive functional group.
[0036] The sulfur-containing polymer has at least one structural unit selected from the group consisting of the structural unit (A) represented by the general formula (1), the structural unit (B) represented by the general formula (2), and the structural unit (C) represented by the general formula (3). The above sulfur-containing polymer preferably contains, as a repeating unit, at least one type of structural unit selected from the group consisting of the above structural unit (A), structural unit (B), and structural unit (C). The sulfur-containing polymer preferably contains a plurality of the structural units (A), (B), and (C), and more preferably contains them as repeating units.
[0037] In the above general formulas (1), (2) and (3), X 1 , X 2 and X 3 are the same or different and each represents a divalent aromatic hydrocarbon group which may have a substituent. Examples of the divalent aromatic hydrocarbon group include a phenylene group, a naphthylene group, an anthrylene group, a triphenylene group, a biphenylene group, a phenanthrylene group, etc. Among them, in terms of reducing the light dispersion of the sulfur-containing polymer, the divalent aromatic hydrocarbon group is preferably a phenylene group, a naphthylene group, an anthrylene group, a biphenylene group, or a triphenylene group, and more preferably a phenylene group.
[0038] Preferred examples of the substituent (hereinafter also referred to as "substituent A") that the divalent aromatic hydrocarbon group may have include reactive functional groups, halogen atoms, alkyl groups, alkoxy groups, aryl groups, aralkyl groups, and sulfur-containing substituents. Examples of the reactive functional group in the above-mentioned substituent A include the same reactive functional groups as those mentioned above.
[0039] Examples of the halogen atom include a fluorine atom, a chlorine atom, a bromine atom, and an iodine atom, with a bromine atom being preferred among these.
[0040] Examples of the alkyl group include a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, an s-butyl group, a t-butyl group, a hexyl group, etc. Among these, an alkyl group having 1 to 18 carbon atoms is preferred, an alkyl group having 1 to 6 carbon atoms is more preferred, and a methyl group is even more preferred.
[0041] Examples of the alkoxy group include a methoxy group, an ethoxy group, a propoxy group, an isopropoxy group, a s-butoxy group, a t-butoxy group, a pentyloxy group, a phenoxy group, a cyclohexyloxy group, a benzyloxy group, etc. Among these, an alkoxy group having 1 to 18 carbon atoms is preferred, an alkoxy group having 1 to 6 carbon atoms is more preferred, and a methoxy group is even more preferred.
[0042] Examples of the aryl group include a phenyl group, a naphthyl group, and a biphenyl group. Of these, a phenyl group is preferable. The number of carbon atoms in the aryl group is preferably 6 to 30, more preferably 6 to 18, and further preferably 6 to 12.
[0043] Examples of the aralkyl group include a benzyl group, a phenethyl group, a phenylpropyl group, a phenylpentyl group, a phenylhexyl group, a phenyloctyl group, etc. The aralkyl group preferably has 7 to 14 carbon atoms, and more preferably has 7 to 9 carbon atoms.
[0044] Examples of the sulfur-containing substituent include a thioalkyl group and a thioaryl group. Among them, a thioalkyl group is preferable. The number of carbon atoms of the sulfur-containing substituent is preferably 1 to 8, more preferably 1 to 6, and further preferably 1 to 4.
[0045] The alkyl group, alkoxy group, aryl group, aralkyl group and sulfur-containing substituent may each have a substituent (hereinafter also referred to as "substituent B"). The substituent B includes the above-mentioned groups other than the reactive functional groups, such as a halogen atom.
[0046] Among these, in terms of being able to further increase the refractive index, the substituent (substituent A) of the divalent aromatic hydrocarbon group is preferably the reactive functional group, a halogen atom, or an alkyl group, alkoxy group, aryl group, aralkyl group, or sulfur-containing substituent which may have a substituent (substituent B), more preferably the reactive functional group, an alkyl group, or a sulfur-containing substituent which may have a substituent (substituent B), still more preferably the reactive functional group, a methyl group, or a thioalkyl group, and particularly preferably the reactive functional group, a methyl group. The above-mentioned substituents may be of only one type or of two or more types. When the above-mentioned substituents are of one type, the substituents may be of one or more types, and when the above-mentioned substituents are of two or more types, each of the substituents may be of one or more types.
[0047] When the divalent aromatic hydrocarbon group is a phenylene group, the substituent on the phenylene group is preferably a hydroxyl group, a carboxyl group, an amino group, an amido group, an imido group, a cyano group, a nitro group, a nitroso group, or a sulfo group, in that a higher refractive index can be achieved. In terms of a possibility of achieving a higher refractive index, the positions of the substituents in the phenylene group are preferably a combination of the 2-position and the 6-position, a combination of the 2-position and the 3-position, a combination of the 2-position and the 4-position, or a combination of the 2-position and the 5-position, and more preferably a combination of the 2-position and the 6-position. Among these, the phenylene group is particularly preferably a phenylene group having hydroxyl groups at positions 2 and 6. Here, position 1 refers to the position of the carbon of the phenylene group that is bonded to the sulfur atom in the structural unit.
[0048] The sulfur-containing polymer preferably further has a substituent capable of imparting amorphousness to the sulfur-containing polymer as a substituent other than the reactive functional group, from the viewpoint of being excellent in both high refractive index and high transparency, more preferably an alkyl group such as a methyl group, an ethyl group, or a propyl group, an alkoxy group such as a methoxy group or an ethoxy group, an aryl group, a sulfur-containing substituent, or a halogen-containing group, and further preferably a methyl group or a methoxy group. The sulfur-containing polymer may have the substituent as the substituent A or as the substituent B.
[0049] The number of the substituents A in the divalent aromatic hydrocarbon group is not particularly limited, but in order to further increase the refractive index of the sulfur-containing polymer, the smaller the number of the substituents A, the more preferable. Specifically, the number of the substituents A is preferably 1 to 6, more preferably 1 to 3, and even more preferably 1.
[0050] The sulfur-containing polymer is preferably composed of the structural unit (A), the structural unit (B), or the structural unit (C) as a repeating unit. The linking positions between these structural units are each represented by X 1 , X 2 , X 3 With respect to the bonding position of -S-, -SO-, and -SO2-, the position may be any one of o-position, m-position, and p-position, and two or more types may be used. From the viewpoint of a high refractive index, the p-position is preferred, and from the viewpoint of solubility, the o-position and m-position are preferred. The sulfur-containing polymer may have two or more types of structural units that are linked to each other at different positions.
[0051] In the above sulfur-containing polymer, the amount of structural units linked at the p-position is preferably 10 mol % or more, and more preferably 30 mol % or more, relative to 100 mol % of all structural units of the polymer, and is preferably less than 99 mol %, more preferably less than 90 mol %, and even more preferably less than 80 mol %.
[0052] The structural unit (A) represented by the above general formula (1) is preferably a structural unit (A-1) represented by the following general formula (1-1).
[0053] [ka]
[0054] (In the formula, R 1 a is the same or different and represents a halogen atom, a reactive functional group, or an alkyl group, an alkoxy group, an aryl group, an aralkyl group, or a sulfur-containing substituent, each of which may have a substituent. 1 It represents the number of and is an integer between 0 and 4.)
[0055] Furthermore, the structural unit (B) represented by the above general formula (2) is preferably a structural unit (B-1) represented by the following general formula (2-1).
[0056] [ka]
[0057] (In the formula, R 2 are the same or different and each represents a halogen atom, a reactive functional group, or an alkyl group, an alkoxy group, an aryl group, an aralkyl group, or a sulfur-containing substituent, each of which may have a substituent. 2 It represents the number of and is an integer between 0 and 4.)
[0058] Furthermore, the structural unit (C) represented by the above general formula (3) is preferably a structural unit (C-1) represented by the following general formula (3-1).
[0059] [ka]
[0060] (In the formula, R 3are the same or different and each represents a halogen atom, a reactive functional group, or an alkyl group, an alkoxy group, an aryl group, an aralkyl group, or a sulfur-containing substituent, each of which may have a substituent. 3 It represents the number of and is an integer between 0 and 4.)
[0061] Above R 1 , R 2 , and R 3 Preferred examples of the halogen atom, reactive functional group, alkyl group, alkoxy group, aryl group, aralkyl group, and sulfur-containing substituent represented by the following formula include the same groups as those mentioned above. Preferred examples of the substituent that these groups may have include the same groups as the substituent B described above.
[0062] a, b, c are R 1 , R 2 , R 3 It represents the number of substituents, and is an integer of 0 to 4, preferably an integer of 0 to 2, and more preferably an integer of 1 to 2.
[0063] The sulfur-containing polymer may be an alternating copolymer of the structural units (A), (B) and (C), or may be a block copolymer or a random copolymer. The sulfur-containing polymer may have one or more of the above structural units (A), (B), or (C).
[0064] The sulfur-containing polymer may be in a form containing only one of the structural units (A), (B) and (C), or may be in a form containing two structural units, or may be in a form containing three structural units. These forms and their content ratios can be appropriately selected depending on the purpose and use of the sulfur-containing polymer. For example, the sulfur-containing polymer preferably contains the structural unit (A) above, and more preferably contains this as a main component, in that this can result in a higher refractive index. In addition, the sulfur-containing polymer preferably contains the structural unit (B) above, and more preferably contains this as a main component, in that this allows for both solubility and a high refractive index. In addition, the sulfur-containing polymer preferably contains the structural unit (C) above, and more preferably contains this as a main component, in that transparency and a high refractive index can be achieved at the same time.
[0065] In view of the above, in the sulfur-containing polymer, the content of the structural unit (A) is preferably 1 to 100 mol %, more preferably 10 to 100 mol %, and even more preferably 50 to 100 mol %, relative to 100 mol % of all structural units of the polymer, from the viewpoint of a high refractive index. In this case, the total content of the structural units (B) and (C) is preferably 0 to 99 mol%, more preferably 0 to 90 mol%, and even more preferably 0 to 50 mol%, relative to 100 mol% of all structural units.
[0066] In the above sulfur-containing polymer, the content of the above structural unit (B) is preferably 1 to 100 mol %, more preferably 10 to 100 mol %, and even more preferably 50 to 100 mol %, relative to 100 mol % of all structural units of the polymer, from the viewpoint of high polarity resulting from solubility. In this case, the total content of the structural units (A) and (C) is preferably 0 to 99 mol%, more preferably 0 to 90 mol%, and even more preferably 0 to 50 mol%, relative to 100 mol% of all structural units.
[0067] In the above sulfur-containing polymer, the content of the above structural unit (C) is preferably 1 to 100 mol %, more preferably 10 to 100 mol %, and even more preferably 50 to 100 mol %, relative to 100 mol % of all structural units of the polymer, from the viewpoint of high transparency. In this case, the total content of the structural units (A) and (B) is preferably 0 to 99 mol%, more preferably 0 to 90 mol%, and even more preferably 0 to 50 mol%, relative to 100 mol% of all structural units.
[0068] In the above sulfur-containing polymer, the total content of the above structural units (A), (B) and (C) is preferably 50 mol% or more, more preferably 80 mol% or more, even more preferably 90 mol% or more, even more preferably 95 mol% or more, and particularly preferably 100 mol%, based on 100 mol% of all structural units of the polymer.
[0069] The sulfur-containing polymer may have a structural unit (D) other than the structural unit (A), the structural unit (B), and the structural unit (C). The sulfur-containing polymer may further have the structural unit (D) as a repeating unit. Examples of the structural unit (D) include structural units having at least the above-mentioned reactive functional groups.
[0070] Examples of the structural unit (D) include structural units derived from a monomer having a polymerizable double bond and the above-mentioned reactive functional group. Examples of the polymerizable double bond include a vinyl group, a (meth)acryloyl group, an allyl group, and a methallyl group, and among these, a (meth)acryloyl group is preferred. Examples of the monomer having the polymerizable double bond and the reactive functional group include carboxyl group-containing (meth)acrylates such as 2-carboxyethyl (meth)acrylate, 2-carboxypropyl (meth)acrylate, 3-carboxypropyl (meth)acrylate, and 4-carboxybutyl (meth)acrylate; phosphate group-containing (meth)acrylates such as 2-(meth)acryloyloxyethyl acid phosphate; epoxy group-containing (meth)acrylates such as glycidyl (meth)acrylate and 3,4-epoxycyclohexylmethyl (meth)acrylate; and vinyl ether group-containing (meth)acrylates such as 2-(2-vinyloxyethoxy)ethyl (meth)acrylate.
[0071] The content of the structural unit (D) is preferably 0 to 80 mol%, more preferably 0 to 50 mol%, even more preferably 0 to 20 mol%, even more preferably 0 to 10 mol%, and particularly preferably 0 to 5 mol%, relative to 100 mol% of all structural units of the polymer.
[0072] The sulfur-containing polymer preferably has an elemental ratio (O / S) of oxygen atoms O bonded to sulfur atoms S in the main chain to sulfur atoms S in the main chain of 0.1 to 1.5. When the elemental ratio is within the above range, the transparency and refractive index become higher. Specifically, the sulfur atom S in the main chain means, for example, the sulfur atom S of -S- in the main chain in the structural unit (A) represented by the above general formula (1), the sulfur atom S of -SO- in the main chain in the structural unit (B) represented by the above general formula (2), and the sulfur atom S of -SO2- in the main chain in the structural unit (C) represented by the above general formula (3). The oxygen atom bonded to the sulfur atom S in the main chain specifically means, for example, the oxygen atom O of -SO- in the main chain in the structural unit (B) represented by the above general formula (2), and means the oxygen atom O of -SO2- in the main chain in the structural unit (C) represented by the above general formula (3).
[0073] The element content ratio (O / S) is more preferably 0.3 or more, and even more preferably 0.7 or more, in order to further increase the transparency, and is more preferably 1.3 or less, and even more preferably 1.1 or less, in order to further increase the refractive index. The above elemental content ratios were measured using an X-ray photoelectron spectroscopy (XPS) , sulfur It can be determined by evaluating and measuring the peak intensity of the 2p orbital (S2p) of the yellow atom, specifically, by the method described in the Examples.
[0074] The sulfur-containing polymer preferably has a glass transition temperature (Tg) of 80 to 250° C. When the glass transition temperature is in the above range, molding can be easily performed. From the viewpoint of increasing heat resistance, the glass transition temperature is more preferably 90° C. or higher, and even more preferably 100° C. or higher, and from the viewpoint of easy molding, it is more preferably 200° C. or lower. The glass transition temperature can be determined by a method in which a differential scanning calorimeter (DSC) is used to measure a temperature rise from room temperature to 250°C (heating rate: 10°C / min) in a nitrogen gas atmosphere, and the DSC curve is obtained by evaluating the intersection point of the tangent line at the baseline and the inflection point.
[0075] The sulfur-containing polymer is S The binding energy is preferably 163 eV to 167 eV. S When the binding energy is within the above range, the refractive index and transparency can be increased. the above S The binding energy can be determined by evaluating the peak top position of the 2p3 / 2 orbital of the sulfur atom obtained by measurement using an X-ray photoelectron spectroscopy (XPS).
[0076] The weight average molecular weight (Mw) of the sulfur-containing polymer is preferably 500 to 10,000,000. When the weight average molecular weight is within the above range, it can be suitably used as an optical material. From the viewpoint of improving mechanical properties, the weight average molecular weight is more preferably 1,000 or more, even more preferably 3,000 or more, and even more preferably 10,000 or more, and from the viewpoint of reducing melt viscosity, it is more preferably 1,000,000 or less, and even more preferably 100,000 or less.
[0077] The polydispersity (weight average molecular weight / number average molecular weight) of the sulfur-containing polymer is preferably 1 to 10. When the polydispersity is within the above range, molding becomes easy. In terms of further improving moldability, the polydispersity is more preferably 5 or less, and further preferably 3 or less.
[0078] The weight average molecular weight and number average molecular weight can be determined by gel permeation chromatography (GPC), specifically, by the method described in the Examples below. The dispersity can be determined by dividing the weight average molecular weight by the number average molecular weight.
[0079] The refractive index of the sulfur-containing polymer is preferably 1.69 or more. When the refractive index is within the above range, the polymer can be suitably used for various applications such as optical materials (members), machine part materials, electric and electronic part materials, automobile part materials, civil engineering and construction materials, molding materials, etc., as well as paint and adhesive materials. The refractive index is more preferably 1.7 or more, and even more preferably 1.71 or more.
[0080] The refractive index can be determined by forming a film having a thickness of 50 nm using the sulfur-containing polymer as a measurement sample, and measuring the film using a spectroscopic ellipsometer UVISEL (manufactured by HORIBA Scientific) with Na D line (589 nm).
[0081] The Abbe number of the sulfur-containing polymer is preferably 10 or more. When the Abbe number is in the above-mentioned range, the light dispersion is small, and the material can be an optical material suitable for lenses and the like. The Abbe number is more preferably 15 or more, even more preferably 18 or more, and even more preferably 20 or more. From the viewpoint of adjusting the light dispersion, the Abbe number is preferably 60 or less, and more preferably 55 or less.
[0082] The Abbe number can be calculated in the same manner as the refractive index by forming a film using the sulfur-containing polymer, measuring the refractive indices at D line (589.3 nm), F line (486.1 nm), and C line (656.3 nm) using the spectroscopic ellipsometer, and using the following calculation formula. Abbe number (v D )=(n D -1) / (n F -n C ) In the formula, n D, n F , n C represent the refractive indices at the Fraunhofer D line (589.3 nm), F line (486.1 nm), and C line (658.3 nm), respectively.
[0083] The sulfur-containing polymer preferably has a visible light transmittance of 70% or more. If the visible light transmittance is within the above range, the polymer can be suitably used as an optical material. The visible light transmittance is more preferably 80% or more, more preferably 85% or more, and even more preferably 88% or more.
[0084] The visible light transmittance is a parallel line transmittance, and can be determined by measuring a range of 400 nm to 700 nm in air without using an integrating sphere using a thin film of the sulfur-containing polymer having a certain thickness (for example, 1 μm) or by standardizing the thickness with a spectrophotometer (for example, a JASCO V-700 series ultraviolet-visible-infrared spectrophotometer) and evaluating the minimum transmittance.
[0085] The sulfur-containing polymer is preferably amorphous for optical material applications requiring transparency. The sulfur-containing polymer has a crystallinity of preferably less than 80%, more preferably less than 50%, even more preferably less than 30%, particularly preferably less than 10%, and most preferably less than 5%. For applications requiring heat resistance that do not require transparency, the crystallinity of the sulfur-containing polymer is preferably 1% or more, more preferably 10% or more, even more preferably 30% or more, and particularly preferably 60% or more. The crystallinity can be determined by measuring with X-ray diffraction (XRD). The crystallinity can be determined by dividing the obtained XRD profile into a plurality of peaks, determining a peak with a half-width of less than 1 as crystalline and a peak with a half-width of 1 or more as amorphous, and calculating the ratio of the area of the crystalline peak to the total peak area as the crystallinity.
[0086] The sulfur-containing polymer is preferably thermoplastic. When the sulfur-containing polymer is thermoplastic, the moldability is improved, such that a thin film can be uniformly formed and a complex shape can be formed with high accuracy, and the polymer can be easily applied to a wide range of applications.
[0087] The sulfur-containing polymer can also form a thermoplastic resin by copolymerization or addition reaction with other monomers by utilizing the reactive functional groups, particularly the curable functional groups. When forming the thermoplastic resin, it is preferable to use a compound (monomer) having a substituent that reacts with the reactive functional group of the sulfur-containing polymer, and the sulfur-containing polymer may be used as the monomer.
[0088] Examples of the substituent of the monomer include ring-opening polymerizable groups such as an epoxy group, an oxetane ring, an ethylene sulfide group, and an aziridine group; radical curable groups and / or addition curable groups such as an acrylic group, a methacrylic group, an allyl group, a vinyl group, and a maleimide group; addition reactive groups such as a hydroxyl group, a thiol group, and a hydrosilyl group; esterification reactive groups such as a carboxylic acid group, an oxazoline group, a hydroxyl group, a thiol group, and an amino group; and urethanization and thiourethanization reactive groups such as an isocyanate group.
[0089] The monomer is preferably a compound having a ring-opening polymerizable group (such as an epoxy group, an oxetane group, or an ethylene sulfide group) that cures by cationic curing, a compound having an acrylic group and / or a methacrylic group that cures by radical curing, or a compound having a vinyl group that cures by an addition reaction such as hydrosilylation or an enethiol reaction. For example, a sulfur-containing polymer having a monofunctional double bond at its terminal can be used to obtain a thermoplastic copolymer by radical polymerization with another monofunctional double bond. A sulfur-containing polymer having a monofunctional thiol group at its terminal can also be used to obtain a thermoplastic polymer by enethiol reaction with the double bond of another polymer.
[0090] <Method of producing sulfur-containing polymer> The method for producing the sulfur-containing polymer of the present invention is not particularly limited as long as it is a method capable of producing a polymer having at least one of the above-mentioned reactive functional groups and the structural units (A) to (C), and includes known polymerization methods, such as a method of polymerizing a monomer component containing a sulfur-containing monomer having the above-mentioned reactive functional group, and a method of polymerizing a monomer component containing a sulfur-containing monomer to obtain a polymer, and then reacting the monomer component with a compound having the above-mentioned reactive functional group to introduce the above-mentioned reactive functional group into the polymer. Among them, the method of reacting a compound having the above-mentioned reactive functional group with a polymer to introduce a functional group is preferred in that the sulfur-containing polymer can be efficiently produced.
[0091] A preferred example of a method for producing the sulfur-containing polymer of the present invention is a method including a step of reacting a sulfur-containing aromatic polymer having a disulfide bond and / or a thiol group at its terminal with a compound having a polymerizable double bond and a reactive functional group. Such a method for producing the sulfur-containing polymer also constitutes one aspect of the present invention.
[0092] An example of the reaction step is a method (method a) in which a terminal disulfide bond of a sulfur-containing aromatic polymer having a disulfide bond at its terminal is cleaved by exposure to light or a radical initiator catalyst, and then the compound having the polymerizable double bond and a reactive functional group is reacted with the compound to bond the compound, thereby introducing a reactive functional group.
[0093] Also included is a method (method b) in which a compound having a polymerizable double bond and a reactive functional group is reacted with a sulfur-containing aromatic polymer having a thiol group at its terminal, and the compound is bonded by a thiol-ene reaction, thereby introducing a reactive functional group.
[0094] Also included is a method (method c) in which a sulfur-containing aromatic polymer having a disulfide bond at its terminal is reacted with a reducing agent such as sodium borohydride, triphenylphosphine, iron trioxide, or iron trioxide to form a thiol group (-SH) at the terminal, and then a compound having the above-mentioned polymerizable double bond and a reactive functional group is reacted to bond the above-mentioned compound by a thiol-ene reaction, thereby introducing a reactive functional group.
[0095] In addition, as a method for producing the above-mentioned sulfur-containing polymer, there can be mentioned a method (method d) in which a reactive functional group is introduced into a sulfur-containing aromatic polymer having a substituent such as a halogen atom (e.g., a halogenated alkyl substituent) by generating a hydroxyl group through a nucleophilic reaction of water.
[0096] Examples of methods for producing the sulfur-containing polymer include a method (method e) of obtaining a polymer from a sulfur-containing monomer having a substituent with a reactive functional group such as a carboxyl group by the method described below, and a method (method f) of introducing a reactive functional group into the sulfur-containing aromatic polymer having a carboxyl group obtained by the above (method e) by generating a hydroxyl group using a reducing agent such as dimethylsulfide borane, borane-tetrahydrofuran complex, or N,N-dimethylaniline borane.
[0097] The above (Method a), (Method b) and (Method c) are preferable methods for producing a sulfur-containing polymer having a reactive functional group at the main chain end. The above (Method d), (Method e) and (Method f) are preferable methods for producing a sulfur-containing polymer having a reactive functional group in the side chain.
[0098] Examples of the polymerizable double bond include a vinyl group, a (meth)acryloyl group, an allyl group, and a methallyl group. The reactive functional group includes the reactive functional groups described above.
[0099] The above-mentioned (Method a) to (Method f) can be appropriately selected depending on the type of reactive functional group to be introduced and the above-mentioned compound to be used. In addition, the reaction conditions and the like may be appropriately selected from known techniques.
[0100] Some preferred examples of the method for producing the sulfur-containing polymer of the present invention will be described below. For example, when a sulfur-containing polymer having a terminal carboxyl group, a phosphoric acid group, a phosphonic acid group, or a curable functional group is produced, the above (method c) is preferred. That is, first, a sulfur-containing aromatic polymer having a disulfide bond at its terminal is treated with a reducing agent such as sodium borohydride to cleave the disulfide bond (-SS-) to form a thiol group at the terminal.
[0101] As the reducing agent, in addition to sodium borohydride, lithium triethylborohydride, triphenylphosphine, Rongalite (sodium formaldehyde sulfoxylate), and the like can be used. The amount of the reducing agent used can be appropriately set depending on the amount of side chains or terminal groups of the sulfur-containing aromatic polymer, and is, for example, preferably 1 to 1,000 parts by mass, more preferably 5 to 300 parts by mass, and even more preferably 10 to 100 parts by mass, relative to 100 parts by mass of the sulfur-containing aromatic polymer.
[0102] The reaction temperature for forming a thiol group from a disulfide bond is preferably 0 to 200° C., more preferably 10 to 100° C. The reaction time is not particularly limited, but is usually 0.1 to 100 hours, preferably 0.5 to 50 hours, more preferably 1 to 24 hours.
[0103] In the reaction for forming the thiol group, a solvent may be used. Examples of the solvent to be used include alcohol-based solvents such as methanol, ethanol, propanol, butanol, methyl cellosolve, butyl cellosolve, and propylene glycol monomethyl ether; ketone-based solvents such as acetone, methyl ethyl ketone, methyl isobutyl ketone, and cyclohexanone; ester-based solvents such as ethyl acetate, isopropyl acetate, butyl acetate, and γ-butyrolactone; ether-based solvents such as diethyl ether, diisopropyl ether, 1,2-dimethoxyethane (DME), and tetrahydrofuran (THF); aromatic hydrocarbon-based solvents such as toluene and xylene; halogenated hydrocarbon-based solvents such as chlorobenzene, fluorobenzene, dichloromethane, chloroform, carbon tetrachloride, 1,2-dichloroethane, and benzotrifluoride; amide-based solvents such as dimethylformamide (DMF), dimethylacetamide, and N-methylpyrrolidone; dimethylsulfoxide (DMSO), nitromethane, and the like.
[0104] Next, the terminal thiol group is reacted with a compound having a polymerizable double bond and a carboxyl group, a phosphoric acid group, a phosphonic acid group, or a curable functional group (two or more polymerizable groups). The compound having the polymerizable double bond and a carboxyl group, a phosphoric acid group, or a phosphonic acid group may be any compound having a polymerizable double bond capable of reacting with a thiol group and a carboxyl group, a phosphoric acid group, or a phosphonic acid group, and examples thereof include a compound having a vinyl group and a carboxyl group, a compound having a (meth)acryloyl group and a phosphonic acid group, a compound having a (meth)acryloyl group and a carboxyl ... and a compound having a (meth)acryloyl group and a phosphoric acid group.
[0105] Specific examples of the above compounds include 4-pentenoic acid, carboxyethyl acrylate, 2-acryloyloxyethyl-succinic acid, 2-acryloyloxyethylhexahydrophthalic acid, 2-acryloyloxyethyl phosphate, vinylphosphonic acid, etc. Among these, 4-pentenoic acid, carboxyethyl acrylate, 2-acryloyloxyethyl phosphate, and vinylphosphonic acid are preferred because they can be made to have a high refractive index and have high reactivity.
[0106] The amount of the compound used can be appropriately set depending on the amount of reactive functional groups to be introduced, and is, for example, preferably 0.1 to 1000 parts by mass, more preferably 1 to 20 parts by mass, and even more preferably 1 to 10 parts by mass, relative to 100 parts by mass of the sulfur-containing aromatic polymer.
[0107] The reaction between the polymerizable double bond and the compound having a carboxyl group, a phosphoric acid group, or a phosphonic acid group is preferably carried out by light irradiation. The light irradiation can be carried out by a known method using a known light source. The reaction can also be carried out using a known polymerization initiator, catalyst, etc., and the type and amount thereof can be appropriately set.
[0108] Furthermore, for example, when the thiolation step is shortened and a reactive functional group is directly introduced, the above (Method a) is preferred. In the above (method a), for example, the sulfur-containing aromatic polymer is directly reacted with the above-mentioned compound having a polymerizable double bond and a carboxyl group, a phosphoric acid group, or a phosphonic acid group.
[0109] In the above (Method a), the amount of the compound having a polymerizable double bond and a carboxyl group, a phosphoric acid group, or a phosphonic acid group used can be appropriately set depending on the amount of reactive functional groups to be introduced, and is, for example, preferably 0.1 to 5,000 parts by mass, more preferably 1 to 100 parts by mass, and even more preferably 1 to 20 parts by mass, relative to 100 parts by mass of the sulfur-containing aromatic polymer.
[0110] In the above (method a), the reaction with the compound having a polymerizable double bond and a carboxyl group is preferably carried out by light irradiation. The light irradiation can be carried out by a known method using a known light source. The reaction can also be carried out using a known initiator, catalyst, etc., and the type and amount thereof can be appropriately set.
[0111] In addition, for example, when using a sulfur-containing polymer having a thiol group, the above (method b) is preferred. The reaction between the sulfur-containing polymer having a thiol group and the compound having the polymerizable double bond and reactive functional group is preferably carried out under the same conditions as the above (method c).
[0112] Furthermore, for example, in the case of producing a sulfur-containing polymer having the above-mentioned reactive functional group in the side chain, the above-mentioned (Method d) or (Method e) is preferred. In the above (Method d), the sulfur-containing aromatic polymer having a substituent such as a halogen atom can be obtained, for example, by adding N-bromosuccinimide and 2,2'-azobis(isobutyronitrile) to a sulfur-containing polymer having an alkyl substituent and reacting them in the production method of a sulfur-containing aromatic polymer described later.
[0113] The reaction temperature is not particularly limited, but is preferably from 10 to 200°C, and more preferably from 50 to 150°C.
[0114] By adding water to the obtained halogenated alkyl group-containing sulfur-containing aromatic polymer, a sulfur-containing polymer having a hydroxyl group on the side chain can be obtained.
[0115] When a sulfur-containing polymer having a carboxyl group on the side chain is produced by the above (Method e), the polymer can be obtained by using a benzenethiol having a carboxyl group, specifically, 2-mercaptobenzoic acid, 3-mercaptobenzoic acid, or the like, as a sulfur-containing monomer in the production method of a sulfur-containing aromatic polymer described later.
[0116] In addition, examples of methods for producing a sulfur-containing polymer having a curable functional group such as a vinyl group in a side chain include a method in which, as described above, N-bromosuccinimide and 2,2'-azobis(isobutyronitrile are added to a sulfur-containing polymer having an alkyl substituent, and the resulting polymer is reacted to obtain a sulfur-containing aromatic polymer having a halogen atom (bromine atom) substituent, and then the resulting polymer is reacted with triphenylphosphine, an aqueous formaldehyde solution, and potassium t-butoxide.
[0117] Furthermore, examples of a method for producing a sulfur-containing polymer having a hydroxyl group in a side chain include a method for producing a sulfur-containing aromatic polymer described below, in which a monomer having an alkoxy group substituent such as a methoxy group is used to obtain a sulfur-containing aromatic polymer having an alkoxy group substituent, and then the polymer is reacted with boron tribromide and water is added.
[0118] In the production method of the present invention, the sulfur-containing aromatic polymer may be one produced by polymerization, or may be a commercially available product.
[0119] The method for producing the sulfur-containing aromatic polymer includes, for example, a method of polymerizing a monomer component containing a sulfur-containing monomer. Preferred examples of the sulfur-containing monomer include disulfide compounds and thiol compounds. More specifically, more preferred examples of the sulfur-containing monomer include diaryl disulfide compounds represented by the following general formula (4) and thioaryl compounds represented by the following general formula (5).
[0120] [ka]
[0121] In the above general formulas (4) and (5), A 1 and A 2 are the same or different and each represents a monovalent aromatic hydrocarbon group which may have a substituent.
[0122] A 1 and A 2Examples of the monovalent aromatic hydrocarbon group represented by the formula (1) include X 1 Examples of the divalent aromatic hydrocarbon group represented by the following formula (1) are monovalent groups, and include a phenyl group, a naphthyl group, an anthryl group, a triphenyl group, a biphenyl group, a phenanthryl group, etc. Among these, a phenyl group, a naphthyl group, an anthryl group, a biphenyl group, or a triphenyl group is preferable, and a phenyl group is more preferable.
[0123] A 1 and A 2 Examples of the substituent possessed by the monovalent aromatic hydrocarbon group represented by the formula (I) include a reactive functional group, a halogen atom, an alkyl group, an alkoxy group, an aryl group, an aralkyl group, a sulfur-containing substituent, etc. Examples of the reactive functional group, the halogen atom, the alkyl group, the alkoxy group, the aryl group, the aralkyl group, and the sulfur-containing substituent include the same groups as those described above.
[0124] The diaryl disulfide compound is preferably a compound represented by the following general formula (4-1). The above thioaryl compound is preferably a compound represented by the following general formula (5-1).
[0125] [ka]
[0126] (In formulas (4-1) and (5-1), R 4 , R 5 , R 6 , R 7 , R 8 , R 9 , R 10 and R 11 are the same or different and each represents a hydrogen atom, a halogen atom, a reactive functional group, or an alkyl group, an alkoxy group, an aryl group, an aralkyl group, or a sulfur-containing substituent, each of which may have a substituent. The halogen atom, the reactive functional group, or the alkyl group, the alkoxy group, the aryl group, the aralkyl group, or the sulfur-containing substituent which may have a substituent is each represented by R 1 The groups represented by the formula (I) are the same as those represented by the formula (I). The substituents which these groups may have include the same as those described above for the substituent B, and among these, halogen atoms are preferred.
[0127] The disulfide compound can also be prepared by oxidation of a thiol compound. Therefore, in the polymerization step, a thiol compound can also be used as a precursor of the disulfide compound. The disulfide compound can be obtained by oxidatively bonding two molecules of a thiol compound.
[0128] The method for obtaining a disulfide compound by oxidizing a thiol compound is not particularly limited, and can be a known method such as a method of oxidation using hydrogen peroxide, iodine, or the like.
[0129] The sulfur-containing monomers may be used alone or in combination of two or more.
[0130] The polymerization is preferably oxidative polymerization. The oxidative polymerization is not particularly limited, and can be carried out by known methods such as a method using a quinone-based compound or a method using a metal compound such as a vanadium compound. Among them, the oxidative polymerization is preferably carried out using a quinone-based oxidizing agent, in terms of improving transparency. It is preferable to use a metal compound, in terms of the amount of use relative to the monomer component being small, resulting in less waste.
[0131] Examples of the quinone-based oxidizing agent include 2,3-dichloro-5,6-dicyano-parabenzoquinone (DDQ), 2,3,5,6-tetrachloroparabenzoquinone (chloranil), 2,3,5,6-tetrabromobenzoquinone (bromanil), 2,3,5,6-tetrafluoroparabenzoquinone, anthraquinone, 1,4-naphthoquinone, 2,3-dichloro-1,4-naphthoquinone, 2,3-dibromo-1,4-naphthoquinone, 2,3-dicyano-1,4-naphthoquinone, 3,4,5,6-tetrachloroorthobenzoquinone (orthochloranil), 3,4,5,6-tetrabromoorthobenzoquinone (orthobromanil), 3,4,5,6-tetrafluorobenzoquinone, etc. Among them, DDQ is preferred because of its high oxidizing power and easy availability. The quinone-based oxidizing agents may be used alone or in combination of two or more.
[0132] The amount of the quinone-based oxidizing agent added is preferably 0.1 to 3 mol, more preferably 0.8 to 1.5 mol, and even more preferably 0.9 to 1.1 mol, per mol of the sulfur-containing monomer used.
[0133] When the quinone-based oxidizing agent is used, an acid may be further added. When the quinone-based oxidizing agent acts on the quinone-based compound, the quinone-based compound becomes a dianion of hydroquinone, but when an acid is added, the dianion can be stabilized and the oxidizing power can be maintained.
[0134] The above-mentioned acid is not particularly limited, and examples thereof include sulfuric acid, acetic acid, methanesulfonic acid, benzenesulfonic acid, toluenesulfonic acid, trifluoromethanesulfonic acid, 1,1,2,2-tetrafluoroethanesulfonic acid, trifluoroacetic acid, perfluoropropionic acid, and perfluorobutyric acid. Among them, trifluoroacetic acid is preferable in terms of increasing the acidity. The above-mentioned acid may be used alone or in combination of two or more.
[0135] The amount of the acid added is preferably 10 to 1000 mol, more preferably 50 to 500 mol, and even more preferably 80 to 120 mol, relative to 100 mol of the total amount of the quinone-based oxidizing agent added.
[0136] The reaction temperature is not particularly limited as long as it is a temperature at which the polymerization proceeds, but from the viewpoint of facilitating the above-mentioned oxidative polymerization, it is preferably 0 to 200°C, more preferably 10°C or higher, and even more preferably 15°C or higher, and from the viewpoint of being able to suppress side reactions, it is more preferably 180°C or lower, and even more preferably 150°C or lower.
[0137] The reaction time is not particularly limited, but is usually 0.1 to 100 hours, preferably 1 to 80 hours, more preferably 5 to 50 hours, and further preferably 10 to 24 hours.
[0138] In the polymerization reaction, a solvent may be used. Preferred solvents include, for example, dichloromethane, chloroform, carbon tetrachloride, 1,2-dichloroethane, tetrachloroethylene, 1,1,2,2-tetrachloroethane, nitromethane, nitrobenzene, chlorobenzene, 1,2-dichlorobenzene, 1,3-dichlorobenzene, N-methylpyrrolidone, tetrahydrofuran, and ethyl acetate.
[0139] In the above polymerization reaction, the monomer components including the sulfur-containing monomer may be added successively during the polymerization reaction. Alternatively, the polymerization may be carried out in multiple stages, for example by oxidatively polymerizing the above-mentioned thiol compound to obtain a disulfide compound, and then oxidatively polymerizing the obtained disulfide compound.
[0140] The method for producing the sulfur-containing polymer may include a step of oxidizing the polymer into which the reactive functional group has been introduced by the above-mentioned step, using an oxidizing agent. By the oxidation step, -S- in the main chain is oxidized to -SO- or -SO2-, and a sulfur-containing polymer having the above-mentioned structural units (B) and / or (C) can be obtained. The oxidizing agent is not particularly limited and any known oxidizing agent can be used. Among them, it is preferable to use a peroxide or chloric acid, since it is possible to appropriately oxidize the sulfide group (-S-) on the main chain to form a sulfoxide (sulfinyl group) (-SO-).
[0141] Examples of the peroxide include metachloroperbenzoic acid, hydrogen peroxide, ammonium persulfate, sodium persulfate, peracetic acid, and t-butyl hydroperoxide. Among them, the oxidizing agent is preferably a peroxide, more preferably metachloroperbenzoic acid or hydrogen peroxide, in that it can be dissolved in the same solvent as the sulfur-containing polymer. The oxidizing agent is further preferably metachloroperbenzoic acid, in that water in which the polymer precipitates is not used and in that oxidation to sulfonyl by an excess of the oxidizing agent is suppressed. When hydrogen peroxide is used as the peroxidizing agent, it is preferable to use a phase transfer catalyst such as trifluoroacetone while reducing the amount of water in order to suppress precipitation of a polymer. The above oxidizing agents may be used alone or in combination of two or more kinds.
[0142] The amount of the oxidizing agent to be added is not particularly limited as long as the desired oxidation reaction of sulfur atoms proceeds, but is usually preferably 0.1 to 10 mol, more preferably 0.5 to 5 mol, and even more preferably 0.8 to 1.5 mol, per 1 mol of sulfur atoms in the sulfur-containing polymer.
[0143] The reaction temperature of the oxidation reaction is not particularly limited as long as it is a temperature at which the desired oxidation reaction proceeds; however, in terms of facilitating the progression of the oxidation reaction, the reaction temperature is preferably 0 to 200°C, more preferably 10°C or higher, and even more preferably 15°C or higher; and in terms of suppressing side reactions, the reaction temperature is more preferably 180°C or lower, and even more preferably 150°C or lower.
[0144] The reaction time is not particularly limited, but is usually 0.1 to 100 hours, preferably 1 to 80 hours, more preferably 5 to 50 hours, and further preferably 10 to 24 hours.
[0145] When oxidation is to be performed to -SO2-, the reaction may be performed for a longer time than the above-mentioned reaction temperature. In this case, the amount of the oxidizing agent added is not particularly limited as long as the oxidation reaction of the desired sulfur atoms proceeds, but is usually preferably 1.5 to 100 mol, more preferably 2 to 50 mol, and even more preferably 2 to 10 mol, per mol of sulfur atoms in the sulfur-containing polymer.
[0146] In the oxidation reaction, a solvent may be used, and preferred examples of the solvent include the same solvents as those used in the polymerization step.
[0147] The polymer obtained by the oxidation step may contain residual acid, and therefore it is preferable to wash the polymer. The washing method is not particularly limited, and includes washing methods using water, acid, base, etc. In addition, in order to remove unreacted substances, the polymer may be passed through a filter or washed with a solvent. The solvent is not particularly limited, and the same solvent as the reaction solvent may be used.
[0148] The method for producing the sulfur-containing polymer may include other steps in addition to the steps described above. Examples of the other steps include an aging step, a neutralization step, a dilution step, a drying step, a concentration step, and a purification step. These steps can be carried out by known methods.
[0149] 2. Sulfur-containing polymer composition The sulfur-containing polymer of the present invention can be combined with other components to form a sulfur-containing polymer composition. The other components are not particularly limited and may be appropriately selected from known components depending on the purpose and use of the sulfur-containing polymer composition.
[0150] The content of the sulfur-containing polymer in the sulfur-containing polymer composition may be appropriately set according to the use and purpose of the sulfur-containing polymer composition, but is preferably 10 to 100% by mass in the total solid content of the sulfur-containing polymer composition (100% by mass), and is more preferably 20% by mass or more, and even more preferably 50% by mass or more, in terms of further improving the transmittance and refractive index. In addition, the content is preferably 99% by mass or less, more preferably 95% by mass or less, even more preferably 85% by mass or less, particularly preferably 80% by mass or less, and most preferably 60% by mass or less, in terms of keeping the viscosity of the sulfur-containing polymer composition low.
[0151] Specific examples of the other components include inorganic substances, crosslinking agents, curing catalysts, curing agents, organic resins, pigments, dyes, antioxidants, ultraviolet absorbers, IR cut agents, reactive diluents, light stabilizers, plasticizers, non-reactive compounds, chain transfer agents, thermal polymerization initiators, anaerobic polymerization initiators, polymerization inhibitors, fillers, adhesion improvers such as coupling agents, heat stabilizers, antibacterial and antifungal agents, flame retardants, matting agents, defoaming agents, leveling agents, wetting and dispersing agents, anti-settling agents, thickening and anti-sagging agents, color separation inhibitors, emulsifiers, slip and scratch prevention agents, anti-skinning agents, drying agents, antifouling agents, antistatic agents, conductive agents (electrostatic assistants), and solvents. These components may be used alone or in combination of two or more. These components may be appropriately selected from known ones and used. The blending amounts of these components may be appropriately set. In particular, the sulfur-containing polymer composition preferably contains the sulfur-containing polymer and at least one selected from the group consisting of an inorganic substance, a crosslinking agent, and an organic resin.
[0152] For example, when the sulfur-containing polymer is combined with an inorganic substance, the properties of the inorganic substance added can be imparted to the composition, and the composition has excellent dispersibility, so that the transparency of the composition can be significantly improved.
[0153] Examples of the inorganic substances include metals, inorganic oxides, inorganic nitrides, inorganic carbides, inorganic sulfides, inorganic hydroxides, etc. The inorganic substances may be used alone or in combination of two or more. The inorganic substance preferably contains a metal.
[0154] Examples of the metals include lithium (Li), sodium (Na), potassium (K), magnesium (Mg), calcium (Ca), manganese (Mn), strontium (Sr), barium (Ba), titanium (Ti), zirconium (Zr), iron (Fe), cobalt (Co), nickel (Ni), copper (Cu), zinc (Zn), aluminum (Al), tin (Sn), and silicon (Si).
[0155] The inorganic oxide is preferably a metal oxide containing a metal element. The metal oxide may be a single metal oxide made of one metal element, a composite oxide made of two or more metal elements, or a solid solution oxide in which a different element is dissolved in the single metal oxide or the composite oxide. The different element may be a metal element or a nonmetal element other than oxygen, such as nitrogen or fluorine. The metal element may be the metal element described above.
[0156] Examples of the single metal oxide include magnesium oxide, calcium oxide, strontium oxide, barium oxide, titanium oxide, zinc oxide, cerium oxide, silicon oxide, tin oxide, zirconium oxide, aluminum oxide, and indium oxide. Examples of the composite oxide include perovskite-type composite oxides such as barium titanate, barium strontium titanate, strontium titanate, barium zirconium strontium titanate, barium zirconium titanate, and lead zirconate titanate; spinel-type composite oxides such as spinel and lithium titanate; and composite oxides such as aluminum titanate. The solid solution oxide may be, for example, a solid solution oxide in which a different metal element and / or a nonmetal element other than oxygen, such as nitrogen or fluorine, is dissolved in the single metal oxide or composite oxide.
[0157] The inorganic nitride is preferably a metal nitride, and examples thereof include boron nitride, carbon nitride, and aluminum nitride. The inorganic carbide is preferably a metal carbide, and examples thereof include silicon carbide, calcium carbide, titanium carbide, and boron carbide. The inorganic sulfide is preferably a metal sulfide, such as copper sulfide, zinc sulfide, or cadmium sulfide. The inorganic hydroxide is preferably a metal hydroxide, and examples thereof include aluminum hydroxide, magnesium hydroxide, and barium hydroxide.
[0158] Among these, the inorganic material is preferably an inorganic oxide, more preferably a metal oxide, in that it has a wide band gap (is transparent to visible light). Furthermore, among the above-mentioned inorganic substances, oxides containing Ti, Zr, Ce, Zn, In, Al, Si, and Sn as main components of metal elements are more preferable, since they have no or little absorption in the visible light region and therefore it is easy to obtain a colorless and transparent composition in which coloring due to the inorganic substance is suppressed. Titanium oxide (TiO2), zirconium oxide (ZrO2), cerium oxide (CeO2), zinc oxide (ZnO), indium oxide (In2O3), aluminum oxide (Al2O3), silicon oxide (SiO2), and tin oxide (SnO2) are particularly preferable.
[0159] Among the inorganic substances, zirconium oxide, titanium oxide, and silicon dioxide are more preferable in terms of further improving the transparency of the sulfur-containing polymer composition and reducing the linear expansion of the composition, and zirconium oxide and titanium oxide are more preferable in terms of improving the refractive index of the sulfur-containing polymer composition. In addition, perovskite-type complex oxides are preferable in terms of having a high relative dielectric constant and being suitable for use as a ferroelectric material or a piezoelectric material. Boron nitride, aluminum hydroxide, and aluminum titanate are preferable in terms of having a high thermal conductivity and being suitable for use as a heat dissipation material.
[0160] From the viewpoint of imparting antistatic properties or electrical conductivity to the sulfur-containing polymer composition while suppressing coloration due to the addition of inorganic substances, a solid solution oxide in which a different metal element or an additive element such as fluorine is solid-solved in zinc oxide (ZnO), indium oxide (In2O3) or tin oxide (SnO2) is preferred. For example, zinc oxide in which In, Al or Ga is solid-solved, indium oxide in which Sn or Ti is solid-solved, tin oxide in which Sb or F is solid-solved, etc. are more preferred.
[0161] The shape of the inorganic material is not particularly limited and may be any of amorphous, particulate, plate-like, fibrous, etc., with particulate being preferred.
[0162] The inorganic material may be surface-treated. The surface treatment is not particularly limited as long as it does not affect the effects of the present invention, and may be a known method such as a method using a silane coupling agent, a method of reacting a compound having a phosphoric acid group, or a method of reacting a compound having a carboxylic acid group.
[0163] The average particle size of the inorganic substance is preferably 1 nm or more and 1000 nm or less. When the average particle size of the inorganic substance is within the above range, the transmittance of the visible light region and the infrared region can be improved. From the viewpoint of reducing the organic resin, the average particle size of the inorganic substance is more preferably 5 nm or more, and even more preferably 10 nm or more. Moreover, the average particle size of the inorganic substance is more preferably 100 nm or less, even more preferably 50 nm or less, and even more preferably less than 30 nm. The inorganic material may be used in combination with two or more different particle sizes in order to achieve closest packing of the inorganic material.
[0164] The average particle size is determined by observing the inorganic material with a SEM (magnification 1000 to 100,000 times, preferably 10,000 times), analyzing the obtained image to determine the particle size (circular area equivalent diameter) of about 10 to 1000 individual particles (primary particles), and evaluating the 50% particle size based on the particle size distribution based on the number. For the image analysis, known image analysis software (for example, Mac-View manufactured by Mountech Co., Ltd.) can be used.
[0165] The content of the inorganic substance is not particularly limited and can be appropriately set according to the purpose and use of the sulfur-containing polymer composition. For example, the content of the inorganic substance is preferably 10 parts by mass or more, more preferably 30 parts by mass or more, even more preferably 50 parts by mass or more, particularly preferably 70 parts by mass or more, and most preferably 80 parts by mass or more, relative to 100 parts by mass of the sulfur-containing polymer, in terms of further improving transparency and reducing linear expansion. In addition, from the viewpoint of reducing the melt viscosity during the production of a resin molded product, the content of the inorganic substance is preferably 90 parts by mass or less, more preferably 80 parts by mass or less, even more preferably 70 parts by mass or less, and even more preferably 50 parts by mass or less, relative to 100 parts by mass of the sulfur-containing polymer.
[0166] The crosslinking agent is not particularly limited, but preferred examples include curable organic compounds having a curable functional group capable of reacting with the reactive functional group of the sulfur-containing polymer. The curable functional group refers to a functional group that undergoes a curing reaction due to heat or light (a group that causes a curing reaction of the polymer composition). Examples of the curable functional group include ring-opening polymerizable groups such as an epoxy group, an oxetane ring, an ethylene sulfide group, and an aziridine group; radical curable groups and / or addition curable groups such as an acrylic group, a methacrylic group, an allyl group, a vinyl group, and a maleimide group; addition reactive groups such as a hydroxyl group, a thiol group, and a hydrosilyl group; esterification reactive groups such as a carboxylic acid group, an oxazoline group, a hydroxyl group, a thiol group, and an amino group; and urethanization and thiourethanization reactive groups such as an isocyanate group.
[0167] The curable organic compound is preferably a compound having a ring-opening polymerizable group (such as an epoxy group, an oxetane group, or an ethylene sulfide group) that cures by cationic curing, a compound having an acrylic group and / or a methacrylic group that cures by radical curing, or a compound having a vinyl group that cures by addition reaction such as hydrosilylation or an enethiol reaction. By using these compounds, the time until primary curing is short, productivity is good, and the obtained cured product has excellent heat resistance (thermal decomposition resistance, heat coloring resistance). Among them, a compound having a ring-opening polymerizable group that cures by cationic curing and a compound having a thiol group that undergoes an enethiol reaction are more preferable in that they have a low shrinkage rate during primary curing and are easy to shape in molding with a mold such as a nanoimprint mold or a resin mold. The compound having the ring-opening polymerizable group may be a compound containing one or more ring-opening polymerizable groups in one molecule, but it is preferable to use a compound having a total of two or more ring-opening polymerizable groups, i.e., a polyfunctional compound. This further enhances the curing reactivity, resulting in a resin composition with excellent curability and curing speed, making it possible to obtain a cured molded product in a shorter time.
[0168] When the reactive functional group of the sulfur-containing polymer is a group having a reactive unsaturated bond, the crosslinking agent used is preferably a crosslinking agent having a thiol group or a crosslinking agent having a reactive double bond. When the reactive functional group of the sulfur-containing polymer is a group having a reactive ionic bond, the crosslinking agent to be used is preferably a crosslinking agent having a thiol group, a crosslinking agent having a reactive ionic bond, or a crosslinking agent having an amine. When the reactive functional group of the sulfur-containing polymer is a hydroxyl group, the crosslinking agent to be used is preferably a crosslinking agent having a reactive double bond, a crosslinking agent having a reactive ionic bond, or a crosslinking agent having an isocyanate group. When the reactive functional group of the sulfur-containing polymer is a thiol group, the crosslinking agent used is preferably a crosslinking agent having a reactive double bond, a crosslinking agent having a reactive ionic bond, or a crosslinking agent having an isocyanate group.
[0169] Examples of the crosslinking agent having a thiol group include aliphatic polythiol compounds such as methanedithiol, 1,2-ethanedithiol, 1,2-bis[(2-mercaptoethyl)thio]3-mercaptopropane, and tris(mercaptoethylthio)methane; 1,2-dimercaptobenzene, 1,3-dimercaptobenzene, 1,4-dimercaptobenzene, 1,3,5-tris(mercaptoethyleneoxy)benzene, and 2,5-toluenedithiol. aromatic polythiol compounds such as 2-methylamino-4,6-dithiol-sym-triazine, 3,4-thiophenedithiol, bismuthiol, 4,6-bis(mercaptomethylthio)-1,3-dithiane, and 2-(2,2-bis(mercaptomethylthio)ethyl)-1,3-dithietane; and heterocyclic polythiol compounds such as 2-methylamino-4,6-dithiol-sym-triazine, 3,4-thiophenedithiol, bismuthiol, 4,6-bis(mercaptomethylthio)-1,3-dithiane.
[0170] Examples of the crosslinking agent having a reactive double bond include compounds having an acrylic group, a methacrylic group, an allyl group, or a vinyl group. Specific examples include aromatic vinyl monomers such as divinylbenzene; aromatic allyl monomers such as diallyl phthalate and diallyl benzene phosphonate; vinyl ester monomers such as polyvinyl acetate; (di)ethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, trimethylolpropane di(meth)acrylate, trimethylolpropane tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol hexa(meth)acrylate, adamantyl (meth)acrylate, fluorene (meth)acrylate, and tris[2-(meth)acryloyloxyethyl]triazine; and triallyl cyanurate.
[0171] Examples of the crosslinking agent having a reactive ionic bond include a compound having an epoxy group, a compound having an oxetane ring, and an episulfide compound. Examples of the compound having an epoxy group include aromatic epoxy compounds such as bisphenol A type epoxy compounds, bisphenol F type epoxy compounds, fluorene-based epoxy compounds, and aromatic epoxy compounds having a bromo substituent; aliphatic epoxy compounds such as those obtained by a condensation reaction between ethylene glycol, diethylene glycol, triethylene glycol, tetraethylene glycol, and polyethylene glycol (PEG600) and epihalohydrin; alicyclic epoxy compounds such as 3,4-epoxycyclohexylmethyl-3',4'-epoxycyclohexanecarboxylate, epsilon-caprolactone-modified 3,4-epoxycyclohexylmethyl 3',4'-epoxycyclohexanecarboxylate, and bis-(3,4-epoxycyclohexyl)adipate; and hydrogenated epoxy compounds such as hydrogenated bisphenol A type epoxy compounds, hydrogenated bisphenol S type epoxy compounds, and hydrogenated bisphenol F type epoxy compounds.
[0172] Examples of the compound having an oxetane ring include aliphatic oxetane compounds such as 1,2-bis[(3-ethyl-3-oxetanylmethoxy)methyl]ethane and dipentaerythritol tetrakis(3-ethyl-3-oxetanylmethyl)ether; and aromatic oxetane compounds such as phenol novolak oxetane, dioxetane compounds having a biphenyl skeleton (ETERNACOLL(R)OXBP, manufactured by Ube Industries), dioxetane compounds having a phenyl skeleton (ETERNACOLL(R)OXTP, manufactured by Ube Industries), and dioxetane compounds having a fluorene skeleton.
[0173] Examples of the episulfide compound include aliphatic episulfide compounds such as bis(2,3-epithiopropyl)sulfide, bis(2,3-epithiopropyl)disulfide, and 1,3-bis(2,3-epithiopropylthio)cyclohexane; aromatic episulfide compounds such as 1,2-bis(2,3-epithiopropylthio)benzene and 1,3-bis(2,3-epithiopropylthio)benzene; and mercapto group-containing epithio compounds such as 3-mercaptopropylene sulfide and 4-mercaptobutene sulfide.
[0174] Examples of the crosslinking agent having an isocyanate group include aliphatic polyisocyanate compounds such as tetramethylene diisocyanate, hexamethylene diisocyanate, lysine triisocyanate, and xylylene diisocyanate; alicyclic polyisocyanate compounds such as isophorone diisocyanate, bis(isocyanatomethyl)cyclohexane, and 4,9-bis(isocyanatomethyl)tricyclodecane; aromatic polyisocyanate compounds such as tolylene diisocyanate, 4,4'-diphenylmethane diisocyanate, diphenylsulfide-4,4-diisocyanate, and phenylene diisocyanate; heterocyclic polyisocyanate compounds such as 4,5-bis(isocyanatomethyl)-1,3-dithiolane; Examples of the polyisothiocyanate compounds include aliphatic polyisothiocyanate compounds such as bis(isothiocyanatoethyl) disulfide; alicyclic polyisothiocyanate compounds such as 3,9-bis(isothiocyanatomethyl)tricyclodecane and 4,8-bis(isothiocyanatomethyl)tricyclodecane; aromatic polyisothiocyanate compounds such as tolylene diisothiocyanate; and sulfur-containing heterocyclic polyisothiocyanate compounds such as 2,5-diisothiocyanatothiophene and 2,5-bis(isothiocyanatomethyl)thiophene.
[0175] The content of the crosslinking agent is preferably 0.1 to 1000 parts by mass, more preferably 1 to 500 parts by mass, even more preferably 5 to 100 parts by mass, and even more preferably 10 to 50 parts by mass, relative to 100 parts by mass of the sulfur-containing polymer.
[0176] In order to promote the reaction between the reactive functional groups of the sulfur-containing polymer and the crosslinking agent, a curing catalyst and / or a curing agent may be included in combination. These can be appropriately selected depending on the reaction.
[0177] Examples of the curing catalyst and curing agent include, for example, a heat latent cationic curing catalyst, a photolatent cationic curing catalyst, a heat latent radical curing catalyst, a photolatent radical curing catalyst, an acid anhydride curing agent, a phenolic curing agent, or an amine curing agent, when performing heat curing or a heating reaction. Among them, it is preferable to use a heat latent cationic curing catalyst or a heat latent radical curing catalyst. In order to reduce the amount of shrinkage of the cured product, it is particularly preferable to use a heat latent cationic curing catalyst. In addition, in order to perform a reaction by irradiation with active energy rays, it is preferable to use a curing agent, a photolatent cationic curing catalyst, or a photolatent radical curing catalyst. In order to reduce the amount of shrinkage of the cured product, it is particularly preferable to use a photolatent cationic curing catalyst. These curing catalysts and cured products can be used alone or in combination of two or more kinds.
[0178] As the above-mentioned heat-latent cationic curing catalyst and photo-latent cationic curing catalyst, onium salts and boron compounds (boron complexes) are preferred.
[0179] As the above-mentioned thermal latent radical curing catalyst, for example, organic peroxides such as cumene hydroperoxide, and azo compounds such as 2,2'-azobis(isobutyronitrile) are suitable.
[0180] Preferred examples of the photolatent radical curing catalyst include acetophenones such as acetophenone and diethoxyacetophenone; benzoins such as benzoin and benzoin methyl ether; benzophenones such as benzophenone and methyl o-benzoylbenzoate; thioxanthones such as 2-isopropylthioxanthone; xanthones; anthraquinones such as 2-methylanthraquinone; and silphosphine oxides.
[0181] The content of the curing catalyst is preferably 0.01 to 10% by mass with respect to 100% by mass of the sulfur-containing polymer composition.
[0182] In curing by irradiation with active energy rays, it is preferable to use a photosensitizer in addition to the above-mentioned photolatent curing catalyst. Preferred examples of the photosensitizer include amines such as triethanolamine, methyldiethanolamine, triisopropanolamine, methyl 4-dimethylaminobenzoate, ethyl 4-dimethylaminobenzoate, isoamyl 4-dimethylaminobenzoate, (2-dimethylamino)ethyl benzoate, (n-butoxy)ethyl 4-dimethylaminobenzoate, and 2-ethylhexyl 4-dimethylaminobenzoate. The amount of the photosensitizer added is preferably 0.1 to 20% by mass relative to 100% by mass of the sulfur-containing polymer composition.
[0183] The curing agent may be an acid anhydride-based, phenol-based or amine-based curing agent that is commonly used. Examples of the acid anhydride curing agent include anhydrides of aliphatic carboxylic acids such as tetrahydrophthalic anhydride and polydodecanedioic anhydride; and aromatic carboxylic acid anhydrides such as phthalic anhydride, trimellitic anhydride, pyromellitic anhydride and biphenyltetracarboxylic anhydride.
[0184] When the above-mentioned acid anhydride, phenol or amine curing agent is used, it is preferable to use a curing accelerator in combination. Examples of the curing accelerator include acid salts of organic bases and aromatic compounds having tertiary nitrogen. Examples of the acid salts of organic bases include organic onium salts such as organic phosphonium salts and organic ammonium salts, and acid salts of organic bases having tertiary nitrogen. Examples of the organic phosphonium salt include phosphonium bromides having four phenyl rings, such as tetraphenylphosphonium bromide and triphenylphosphine toluene bromide. Examples of the organic ammonium salt include tetra(C1-C8)alkylammonium bromides such as tetraoctylammonium bromide, tetrabutylammonium bromide, and tetraethylammonium bromide. Examples of the acid salt of an organic base having a tertiary nitrogen include organic acid salts of alicyclic bases having a tertiary nitrogen in the ring and organic acid salts of various imidazoles. The above curing accelerators may be used alone or in combination of two or more kinds. The amount of the curing accelerator used is preferably 0.01 to 5% by mass, and more preferably 0.03 to 3% by mass, relative to 100% by mass of the sulfur-containing polymer composition.
[0185] The organic resin is not particularly limited as long as it is other than the sulfur-containing polymer, and conventionally known polymer materials can be used, such as polyolefins such as polyethylene, polypropylene, and cyclic polyolefins; vinyl polymers such as polyvinyl chloride, polyvinylidene chloride, polystyrene, polyvinyl acetate, and polyvinyl alcohol; (meth)acrylic resins; polyurethanes; fluororesins such as polytetrafluoroethylene; ABS resins; AS resins; polyamides; polyacetals; polycarbonates; modified polyphenylene ethers; polyesters such as polyethylene terephthalate and polybutylene terephthalate; amorphous polyarylates; liquid crystal polymers; polyether ether ketones; polyimides; silicone resins; polyamideimides; cellulose-based polymers; epoxy resins; urea resins; melamine resins; phenolic resins; urethane resins; unsaturated polyester resins; diallyl phthalate resins; alkyd resins; and fluorene-containing resins. Among these, polystyrene, polycarbonates, fluorene-containing resins, and cyclic polyolefins are preferred.
[0186] When the organic resin is contained, the content of the organic resin is preferably 10% by mass or more, more preferably 30% by mass or more, and even more preferably 50% by mass or more, based on 100% by mass of the total solid content of the sulfur-containing polymer composition, in order to increase the refractive index. In addition, from the viewpoint of improving curability and heat resistance, the content of the organic resin is preferably less than 90% by mass, more preferably less than 80% by mass, and even more preferably less than 70% by mass, based on 100% by mass of the total solid content of the sulfur-containing polymer composition.
[0187] The glass transition temperature (Tg) of the sulfur-containing polymer composition is preferably 80 to 250° C. When the glass transition temperature is in the above-mentioned range, molding can be easily performed. From the viewpoint of increasing heat resistance, the glass transition temperature is more preferably 90° C. or higher, and even more preferably 100° C. or higher, and from the viewpoint of easy molding, it is more preferably 200° C. or lower. The glass transition temperature can be determined by the same method as the above-mentioned method for measuring the glass transition temperature of the sulfur-containing polymer.
[0188] The refractive index of the sulfur-containing polymer composition is preferably 1.69 or more. When the refractive index is in the above range, it can be suitably used as an optical material, etc. The refractive index is more preferably 1.70 or more, and further preferably 1.71 or more. The refractive index can be determined by the same method as the above-mentioned method for measuring the refractive index of the sulfur-containing polymer.
[0189] The Abbe number of the sulfur-containing polymer composition is preferably 10 or more. When the Abbe number is in the above-mentioned range, the light dispersion is small, and the composition can be an optical material suitable for lenses and the like. The Abbe number is more preferably 15 or more, even more preferably 18 or more, and even more preferably 20 or more. From the viewpoint of adjusting the light dispersion, the Abbe number is more preferably 60 or less, and even more preferably 55 or less. The Abbe number can be determined by the same method as the above-mentioned method for measuring the Abbe number of the sulfur-containing polymer.
[0190] The visible light transmittance of the sulfur-containing polymer composition is preferably 70% or more. When the visible light transmittance is within the above range, it can be suitably used as an optical material. The visible light transmittance is more preferably 80% or more, more preferably 85% or more, and even more preferably 88% or more. The above-mentioned visible light transmittance is a parallel line transmittance, and can be determined by the same method as the above-mentioned method for measuring the visible light transmittance of the sulfur-containing polymer.
[0191] The density of the sulfur-containing polymer composition is 1.1 g / cm when the inorganic material is not contained, in that the refractive index can be made higher. 3 It is preferable that the content is 1.3 g / cm or more. 3 More preferably, it is 1.4 g / cm or more. 3 More preferably, it is 1.6 g / cm or more. 3 More preferably, it is 1.8 g / cm or more. 3 On the other hand, in terms of being lightweight, the density of the sulfur-containing polymer composition is particularly preferably 3.0 g / cm or more. 3 Preferably less than 2.5 g / cm 3 More preferably, it is less than 2.0 g / cm 3 It is even more preferable that it is less than 1000 .mu.m.
[0192] The method for producing the sulfur-containing polymer composition is not particularly limited, and the sulfur-containing polymer composition can be obtained by mixing the sulfur-containing polymer with the inorganic substance and other components as necessary. The mixing can be performed by known means such as a bead mill, a roll mill, a ball mill, a jet mill, a kneader, or a blender.
[0193] The sulfur-containing polymer composition is preferably thermoplastic. Since the sulfur-containing polymer composition contains the sulfur-containing polymer, it has a high refractive index and required properties such as heat resistance. When the sulfur-containing polymer composition is thermoplastic, it has good moldability and can be easily applied to various applications requiring the above-mentioned properties.
[0194] The curing method of the sulfur-containing polymer and the sulfur-containing polymer composition is not particularly limited, and may be performed by a known method such as heating, irradiation with active energy rays, or a combination thereof. The curing method may be appropriately selected depending on the reactive functional group of the sulfur-containing polymer and the purpose and use of the sulfur-containing polymer composition.
[0195] The heating method is not particularly limited, but examples thereof include a method at 40 to 400° C. for 30 seconds to 48 hours, preferably at 50 to 300° C. for 10 minutes to 30 hours, and more preferably at 120 to 260° C. for 30 minutes to 3 hours.
[0196] The active energy ray is not particularly limited, and known active energy rays such as electron beams, ultraviolet rays, visible light, etc. The amount of active energy rays to be irradiated is not particularly limited, and may be appropriately set depending on the purpose and use of the sulfur-containing polymer and the sulfur-containing polymer composition.
[0197] The sulfur-containing polymer and the cured product obtained by curing the sulfur-containing polymer composition have a high refractive index and various properties based on the reactive functional group of the sulfur-containing polymer, and can be suitably used for optical applications, etc. The present invention also includes a cured product of the sulfur-containing polymer. The present invention also includes a cured product of the sulfur-containing polymer composition.
[0198] 3.Applications The sulfur-containing polymer and the sulfur-containing polymer composition of the present invention are used in various applications, both optical and non-optical, and are preferably used for optical applications. Specifically, they are used for various applications, such as imaging lenses, optical materials (members), machine part materials, electric and electronic part materials, automobile part materials, civil engineering and construction materials, molding materials, and the like, as well as paints and adhesive materials. In particular, they are preferably used for optical materials, optical device members, display device members, and the like. Specific examples of such applications include optical applications such as eyeglass lenses, imaging lenses for cameras such as (digital) cameras, mobile phone cameras, and in-vehicle cameras, light beam focusing lenses, and light diffusing lenses, LED encapsulants, optical adhesives, optical pressure-sensitive adhesives, optical transmission bonding materials, filters, diffraction gratings, diffractive optical elements, prisms, light guides, watch glasses, and transparent glasses and cover glasses for display devices; optical device applications such as photosensors (optical sensors (CMOS sensors, TOF sensors, etc.)), photoswitches, LEDs, micro LEDs, light emitting elements, optical waveguides, multiplexers, splitters, disconnectors, optical splitters, and optical fiber adhesives; and display device applications such as substrates for display elements such as LCDs, organic electroluminescence (EL), and PDPs, substrates for color filters, substrates for touch panels, index matching materials used in touch panels, etc., hard coats, brightness enhancing films, prism films, lenticular sheets, microlens sheets, display protective films, display backlights, light guide plates, anti-reflection films, anti-fogging films, and light extraction enhancers for LEDs, organic electroluminescence, etc.
[0199] In addition, the sulfur-containing polymer and the sulfur-containing polymer composition of the present invention have excellent heat resistance, and therefore can be suitably used for heat-resistant materials, ferroelectric materials, heat-dissipating materials, separators for battery materials, filters such as gas separation membranes and liquid separation membranes, and the like. In addition, the sulfur-containing polymer and the sulfur-containing polymer composition of the present invention have a wide range of no absorption in the visible and infrared regions, and are therefore suitable for use as optical materials in the visible and infrared regions. In addition, because of their excellent heat resistance, they can also be used as battery components such as electrode materials for fuel cells and Li batteries, and electrolyte materials. In addition, they can also be used as insulating materials, antenna materials, etc., making use of their low dielectric properties.
[0200] The sulfur-containing polymer and the sulfur-containing polymer composition of the present invention can be suitably used as a molding material. Examples of molding methods include conventionally known injection molding, T-die method, inflation method, imprint molding, nanoimprint molding, and other molding using a mold or resin mold. The desired shape may be formed by a casting method, coating method, or other method. The shape is not particularly limited, and examples thereof include various known shapes such as lenses, sheets, and films. The sulfur-containing polymer and the sulfur-containing polymer composition of the present invention can be suitably used in etching processes such as plasma etching and resist processes utilizing solubility differences, and can also be suitably used in coating processes such as spin coating, bar coating, squeegee coating, and inkjet coating. The sulfur-containing polymer composition of the present invention is preferably a thermoplastic resin composition in that it has good processability, and is preferably a curable resin composition in that it has a low viscosity and has good conformability to fine metal molds and resin dies during molding.
[0201] As described above, the sulfur-containing polymer and the sulfur-containing polymer composition of the present invention have a high refractive index and can have various properties according to the purpose. Therefore, they can be suitably used in a wide range of applications including optical applications. EXAMPLES
[0202] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples. In addition, unless otherwise specified, "parts" means "parts by mass" and "%" means "% by mass".
[0203] In the examples, each evaluation was carried out by the following methods. <Weight average molecular weight (Mw), number average molecular weight (Mn), dispersity (Mw / Mn)> The weight average molecular weight and number average molecular weight of the polymer were determined by gel permeation chromatography (GPC) under the following conditions. The dispersity was calculated by dividing the weight average molecular weight by the number average molecular weight. Equipment: SHIMAZU, CBM-20A Detector: Refractive index detector (RI) (SHIMAZU, SPD-20MA), and UV-Vis-Infrared spectrophotometer (SHIMAZU, SPD-20MA) Column: TOSOH, TSKgel SuperHM-N Column temperature: 40℃ Flow rate: 0.3ml / min Calibration curve: Polystyrene Standards Eluent: Chloroform
[0204] < 1 H-NMR, 13 C-NMR, DOSY-NMR> The obtained polymer was subjected to the following conditions: 1 H-NMR, 13 C-NMR and DOSY-NMR measurements were performed. Equipment: Agilent Technologies nuclear magnetic resonance spectrometer (600MHz) Measurement solvent: deuterated chloroform Sample preparation: Several mg to several tens of mg of the obtained polymer was dissolved in a measurement solvent.
[0205] <ir> IR measurements were carried out under the following conditions. Equipment: JASCO Fourier transform infrared spectrophotometer (FT / IR-6100) Sample preparation: Approximately 2 mg of sample was mixed with approximately 300 mg of dry potassium bromide (KBr), and the mixture was ground in a mortar and pestle and molded.
[0206] <Refractive index (n D )> The phase difference and reflection deviation ratio of the polarized light before and after incidence of the obtained film were measured using a UVISEL spectroscopic ellipsometer manufactured by HORIBA Scientific Co., Ltd. The complex refractive index was obtained using preset values for the wavelength (450 nm) and incident angle (75°) of the incident light, and the refractive index at 190-2000 nm was calculated, and the refractive index at a wavelength of 589.3 nm was obtained. Unless otherwise specified, 30 mg of the sulfur-containing polymer or sulfur-containing polymer composition was dissolved in 1,1,2,2-tetrachloroethane (1 ml), passed through a membrane filter having a pore size of 0.2 μm, and 0.4 ml of the solution that passed through the filter was drop-cast onto a glass substrate (2 cm × 2 cm) to obtain a film having a thickness of about 50 nm, which was then measured.
[0207] <Abbe number (v D )> The refractive index of the obtained film was measured using a spectroscopic ellipsometer UVISEL manufactured by HORIBA Scientific Co., Ltd., with D line (589.3 nm), F line (486.1 nm), and C line (656.3 nm), and the Abbe number (v D ) was sought. Abbe number (v D )=(n D -1) / (n F -n C ) (A) In the formula, n D , n F , n C indicate the refractive indices at the Fraunhofer D line (589.3 nm), F line (486.1 nm), and C line (656.3 nm), respectively. Unless otherwise specified, a film having a thickness of 50 nm was obtained in the same manner as in the measurement of the refractive index described above, and this was measured.
[0208] <Glass transition temperature (Tg)> A Seiko Electric Industry Co., Ltd. differential scanning calorimeter was used, and α-alumina was used as a reference. The DSC curve was obtained by heating from room temperature to 250°C at a heating rate of 10°C / min, and the evaluation was performed based on the intersection of the tangent line at the baseline and the inflection point.
[0209] <Element content ratio O / S ratio> A sample was prepared by spin-coating 0.25 ml of the polymer solution onto a silicon wafer to form a film, and a photoelectron spectrometer (JPS-9010TR, XPS device, light source: Mg, X-ray output: 400 W) manufactured by JEOL was used. , heavy The elemental content ratio (O / S ratio) of oxygen atoms bonded to sulfur atoms in the main chain of the polymer to sulfur atoms in the main chain was calculated. 。 The measurement method and the position of the binding energy were based on Handbook of X-ray Photoelectron Spectroscopy (published by JEOL in March 1991).
[0210] <Binding energy> A sample was prepared by spin-coating 0.25 ml of the polymer solution onto a silicon wafer to form a film. The binding energy was measured from the peak position of the 2p3 / 2 orbital of the sulfur atom using a JEOL photoelectron spectrometer (JPS-9010TR, XPS device).
[0211] <Thin film transmittance (T%)> The transmittance of the obtained thin film was measured by a spectrophotometer (UV-Vis-Infrared Spectrophotometer V-700 series manufactured by JASCO Corporation). To evaluate the visible light transmittance, the transmittance at 400 nm and the average transmittance from 400 to 700 nm were compared. Note that in Examples 7, 9, 10, and 11, a glass substrate was used as a control, and in the other cases, air was used as a control sample. Unless otherwise specified, a solution was prepared by dissolving the polymer in an organic solvent at about 5%. The resulting solution was spin-coated at about 500 rpm for 60 seconds onto a glass substrate that has almost no absorption of visible light, and then dried at 100°C for 10 minutes to form a thin film (1 μm thick). The drop-cast film shows the transmittance at the measured film thickness.
[0212] Example 1 <Sulfur-containing polymer 1> (Synthesis of methoxy-substituted polyphenylsulfide resin (OMePPS)) In a 1000 mL conical beaker, chloroform (300 mL) and 2-methoxybenzenethiol (28.0 g, 0.2 mol) were added, and then a methanol solution (300 mL) containing iodine (25.4 g, 0.1 mol) was added, followed by stirring at room temperature for 1 hour. Then, an aqueous sodium thiosulfate solution was added to remove the iodine, and the solvent was distilled off. The reaction solution was dispersed in diethyl ether, and separated and washed in the order of an aqueous hydrochloric acid solution (3 mass%), an aqueous sodium hydroxide solution (5 mass%), and pure water, followed by dehydration, solvent removal, and vacuum drying to obtain bis(2-methoxyphenyl)disulfide.
[0213] The obtained bis(2-methoxyphenyl) disulfide (5.568 g, 20 mmol) was added to a dichloromethane solution (20 mL) of 2,3-dichloro-5,6-dicyano-parabenzoquinone (DDQ, 1 M) and trifluoroacetic acid (1 M) in a 50 mL three-neck flask, and oxidative polymerization was performed by stirring at room temperature for 20 hours. After removing by-products in the polymerization solution with a glass filter, the polymerization solution was dropped into hydrochloric acid-acidified methanol to precipitate the generated polymer, and the precipitate was collected as a powder by filtering with a glass filter. The resin was then washed with an aqueous potassium hydroxide solution (0.1 M), pure water, and methanol in that order, and dried in vacuum to synthesize methoxy-substituted polyphenyl sulfide resin (OMePPS). The molecular weight was Mw=4200, and the dispersity was 1.7. The glass transition temperature Tg was 118°C, the 5% weight loss temperature Td5% was 317°C, and the molar extinction coefficient ε was 6.2×10 2 L / (mol cm), the refractive index was 1.73, and the Abbe number was 22. OMePPS is amorphous and soluble in chloroform, tetrahydrofuran, N,N'-dimethylacetamide, and N,N'-dimethylformamide, making it possible to form a transparent thin film by drop casting.
[0214] (Synthesis of thiol-terminated methoxy-substituted polyphenylsulfide resin (SH-OMePPS)) The above OMePPS (2.0 g) was added to a 100 mL three-neck flask and dissolved in tetrahydrofuran (THF, 40 mL). Sodium borohydride (2 g, excess amount) was added, and methanol (1 mL) was added dropwise with stirring. The mixture was then heated to reflux at 65°C for 20 hours. After the reaction was completed, the mixture was purified by precipitation in hydrochloric acid-acidified methanol (600 mL, containing 5 vol% hydrochloric acid), filtered with a glass filter, and washed with methanol and water. After overnight vacuum drying (25°C, 12 hours), thiol-terminated methoxy-substituted polyphenylsulfide resin (SH-OMePPS) was obtained (yield 81%, terminal thiol concentration 100%).
[0215] (Synthesis of carboxyl-terminated methoxy-substituted polyphenylsulfide resin (COOH-OMePPS)) The above SH-OMePPS (1.3 g, -SH group concentration 0.6 mmol, 1 eq) was added to a 10 mL eggplant flask and dissolved in dimethylformamide (DMF, 3 mL), after which 4-pentenoic acid (600 mg, 6 mmol, 10 eq) and 2,2-dimethoxy-2-phenylacetophenone (DMPA, 31 mg, 0.12 mmol, 0.2 eq) were added. After five freeze-degassing (Ar gas) cycles, the mixture was irradiated with UV light at room temperature for 4 hours to cause a thiol-ene reaction (Hg lamp, hν = 365 nm). After the reaction, the solution was diluted with DMF (10 mL) and then precipitated in hydrochloric acid-acidified methanol (300 mL, containing 5 vol% hydrochloric acid). The precipitate was filtered through a glass filter, washed with methanol and water, and vacuum dried overnight (25°C, 12 hours) to obtain a carboxyl-terminated methoxy-substituted polyphenylsulfide resin (COOH-OMePPS) (sulfur-containing polymer 1) (yield 88%, terminal carboxylic acid concentration 90%). Infrared spectrophotometer (IR) measurements showed that only SH-OMePPS has an emission wavelength of 2560 cm -1 The absorption of SH stretching vibration was observed at 1740 cm for COOH-MePPS only. -1 The C=O stretching vibration was confirmed. The introduction rate of carboxylic acid into COOH-MePPS was 89% by neutralization titration. The chemical reaction formula for synthesizing COOH-OMePPS from OMePPS is shown below. The physical properties of the obtained polymers are shown in Table 1.
[0216] [ka]
[0217] [Table 1]
[0218] From Table 1, it was confirmed that COOH-OMePPS, which is a sulfur-containing polymer having a carboxyl group, is a high refractive index material having a refractive index of 1.7 or more.
[0219] <Preparation of titanium oxide hybrid film of sulfur-containing polymer 1 by sol-gel method> The above COOH-OMePPS (0.0274 g) was added to a 10 mL sample bottle, dissolved in dimethylacetamide (1.5 mL), and then hydrochloric acid (37 mass%, 25 μL) was added and stirred at room temperature for 30 minutes. In a glove box, tetrabutyl orthotitanate (50 μL) was dissolved in 1-butanol (100 μL) in advance to prepare a solution, which was then dropped into the stirred polymer solution and reacted for an additional 30 minutes. After the reaction, impurities were removed using a membrane filter, and the reaction solution was diluted with dimethylacetamide so that the solute concentration was 60 mg / mL or 15 mg / mL, and a hybrid solution (sulfur-containing polymer composition) was prepared. The hybrid solution (solute concentration 60 mg / mL solution) was dropped onto a silicon wafer and spin-coated at 2000 rpm for 20 seconds. The wafer was then heat-treated at 0.08 MPa and 60°C for 4 hours and then at 0.08 MPa and 150°C for 3 hours to obtain a hybrid film (thickness 0.13 μm). In addition, a hybrid solution (solute concentration 15 mg / mL, 400 μL) was dropped onto a glass substrate and heat-treated at 0.08 MPa and 60°C for 4 hours and then at 0.08 MPa and 150°C for 3 hours to obtain a hybrid film (thickness 5.5 μm). IR measurement shows 3400cm -1 The absorption due to the -OH group on the TiO2 domain surface was observed at 610 cm -1 The formation of TiO2 was confirmed by observing absorption of Ti-O-Ti stretching vibration. Table 2 shows various physical properties of the hybrid solutions with the above COOH-OMePPS having different TiO2 contents (Experimental Examples 1-1 to 1-4). The refractive index and Abbe number were measured for the hybrid films formed on silicon wafers. Figure 1 shows photographs of hybrid films formed on glass substrates using sulfur-containing polymer compositions with different blending ratios of sulfur-containing polymer and TiO2. Figure 1 (a) shows, from the left, the cases where the solid mass ratio of (COOH-OMePPS / TiO2) is (100 / 0), (90 / 10), (70 / 30), and (50 / 50), and (b) shows the case where the mass ratio of (OMePPS / TiO2) is (80 / 20).
[0220] [Table 2]
[0221] From Table 2, the COOH-OMePPS hybrid membrane with 50 mass% TiO2 has n D = 1.85, and Tg 136°C. From these, it was confirmed that the polymer composition containing COOH-OMePPS and a metal oxide has a high refractive index and is excellent in transparency and heat resistance. Furthermore, Figure 1 shows that (a) COOH-OMePPS, which contains reactive functional groups, maintains transparency and has a high refractive index even when 50% TiO2 is added. On the other hand, (b) OMePPS, which does not contain reactive functional groups, becomes cloudy when 20% TiO2 is added. This shows that the introduction of carboxyl groups contributes to improved transparency.
[0222] Example 2 <Sulfur-containing polymer 2> (Synthesis of methyl-substituted polyphenylsulfide resin (methyl-substituted PPS)) A methyl-substituted polyphenylsulfide resin (MePPS) was obtained by the same synthesis method as described above (Synthesis of OMePPS), except that in Example 1, m-toluenethiol was used instead of 2-methoxybenzenethiol to obtain bis(3-methylphenyl)disulfide, which was then used to synthesize a polymer.
[0223] (Synthesis of methyl-substituted PPS containing carboxyl groups) The resulting methyl-substituted PPS and an acrylic acid monomer (2-carboxyethyl acrylate) were mixed in a mass ratio of 5 / 1 or 3 / 1, degassed, and then irradiated with light from a UV lamp (Ushio Inc. SP-9, light source: Xe, Hg) (wavelength: 230 nm to 320 nm, illuminance: 30 mW / cm 2 ), and purification by precipitation in acidic methanol was performed to obtain a methyl-substituted PPS having a polycarboxylic acid at the end (carboxyl group-containing methyl-substituted PPS) (sulfur-containing polymer 2) as a white powder. The synthesis reaction formula for the carboxyl group-containing methyl-substituted PPS is shown below. In the formula, (1) represents the methyl-substituted PPS, and (4) represents the carboxyl group-containing methyl-substituted PPS. 1 The introduction rate was calculated by H-NMR, and a peak derived from methyl-substituted PPS and a peak derived from acrylic acid were observed on the same diffusion coefficient by DOSY-NMR, confirming the formation of a copolymer. Table 3 shows various physical properties of MePPS and the obtained carboxyl group-containing methyl-substituted PPS (Experimental Examples 2-1 to 2-3). The refractive index of the obtained polymer decreased with the introduction of acrylic acid units, but all were high values of 1.7 or more.
[0224] [ka]
[0225] [Table 3]
[0226] <Preparation of nanoparticle dispersion of methyl-substituted PPS containing carboxyl groups> 20 μL of a zirconia nanoparticle-dispersed methyl ethyl ketone solution (ZP-153, manufactured by Nippon Shokubai Co., Ltd., concentration 70% by mass) was mixed with 1 mL (30 mg / mL) of the obtained toluene solution of the carboxyl group-containing methyl-substituted PPS to obtain a nanoparticle dispersion (sulfur-containing polymer composition). The obtained dispersion was spin-coated on a silicon wafer or drop-cast on a glass substrate to form a film (film thickness: about 0.1 μm). It was visually confirmed that fine particles were dispersed in the nanoparticle dispersion and thin film obtained above. The refractive index of the nanoparticle dispersion was 1.73.
[0227] Comparative Example 1 In preparing the nanoparticle dispersion, the same procedure as in Example 2 was repeated except that the above-mentioned methyl-substituted PPS was used instead of the carboxyl group-containing methyl-substituted PPS, and a nanoparticle dispersion was obtained and used to form a film (Comparative Example 1).
[0228] Fig. 2 is a photograph of the nanoparticle dispersion obtained above, and Fig. 3 is a photograph of a hybrid membrane obtained using the nanoparticle dispersion. In Fig. 2 and Fig. 3, (a) is the nanoparticle dispersion containing the carboxyl group-containing methyl-substituted PPS of Example 2 or the hybrid membrane obtained using the same, and (b) is the nanoparticle dispersion containing the methyl-substituted PPS of Comparative Example 1 or the hybrid membrane obtained using the same. As a result, it was found that the sulfur-containing polymer compositions of the Examples have a higher refractive index and are more transparent than the sulfur-containing polymer compositions of the Comparative Examples. It was also found that the inclusion of nanoparticles results in a lower linear expansion coefficient.
[0229] Example 3 (Surface modification of zirconia nanoparticles) Referring to S. Kawaguchi et.al., Macromolecules, 2017, 50, 9713-9725, p-toluic acid (0.15 g, 23% relative to nanoparticles), methanol (15 mL), toluene (0.5 mL), and zirconia (ZrO2) nanoparticle aqueous dispersion (manufactured by ITEC, average particle size 4 nm, 30% by mass) (1.8 g, nanoparticles 0.54 g) were added to a 100 mL flask and stirred at room temperature for 2 hours. A methanol-toluene mixed solution (volume ratio of methanol / toluene = 7 / 3) was added (about 20 mL), the solvent was removed to a total amount of about 5 mL using an evaporator, and the methanol-toluene mixed solution was added again and the solvent was removed again. This operation was repeated about six times while changing the methanol volume ratio from 70% to 100%. Acetone was added to the obtained surface-modified zirconia nanoparticles, and the unreacted components were removed by removing the supernatant, and surface-modified zirconia nanoparticles were obtained. From IR measurement, 1690 cm from carboxylic acid -1 The decrease in the peaks around 1550 and 1450 cm due to the carboxylate group -1 , Zr-OC-derived 1100cm -1 The rise of the peak confirmed the surface modification of zirconia nanoparticles with p-toluic acid. The modification ratios WF and M were calculated using a thermogravimetric differential thermal analyzer (TG-DTA, Rigaku Corporation, TG8120). The modification ratio was 18% by mass. Dynamic light scattering (DLS, Malvern, Zetasaizer Nano ZS) suggested that the surface-modified zirconia nanoparticles were aggregated in toluene to a particle size of about 6 orders of magnitude (average particle size: 3 nm).
[0230] (Optical properties of hybrid films) Each amount of the surface-modified zirconia nanoparticles obtained above was added to toluene and dispersed with a homogenizer for about 5 minutes to obtain a toluene dispersion of zirconia nanoparticles. The carboxyl group-containing methyl-substituted PPS (30 mg / ml) obtained in Example 2 above was added to the obtained dispersion in the compounding ratio shown in Table 4 and mixed. The obtained mixed solution (sulfur-containing polymer composition) was drop-cast onto a glass substrate to form a film (thickness 3 μm) to prepare a hybrid film. Spectroscopic ellipsometry and UV-vis measurements showed that the ZrO2 content was 16.4% (ZrO2 / 1) and the film had good optical properties (n D =1.73,v D =23,%T=84%) was shown.
[0231] Comparative Example 2 A dispersion was prepared and a hybrid membrane was produced in the same manner as in Example 3, except that the methyl-substituted PPS of Comparative Example 1 was used instead of the carboxyl group-containing methyl-substituted PPS in Example 3.
[0232] Table 4 shows various physical properties of the hybrid membranes obtained in Example 3 and Comparative Example 2. In Table 4, Experimental Examples 3-1 to 3-4 are the hybrid membranes of Example 3, and Experimental Example 3-5 is the hybrid membrane of Comparative Example 2.
[0233] [Table 4]
[0234] In Table 4, polymer 2 is a carboxyl group-containing methyl-substituted PPS (Mw=2.8×10 4 , acrylic acid monomer unit / (MePPS unit+acrylic acid monomer unit)=0.18), and polymer 1 represents methyl-substituted PPS. In the evaluation of dispersibility, "◯" indicates "dispersed" and "×" indicates "cloudy." Refractive index (n D ) (calculated value) was calculated based on the Lorenz-Lorenz effective medium theory (n DZrO2 =2.13,n Dpolymer =1.70,n Dmodifer =1.52,ρ ZrO2 =5.68g / cm 3 ,ρ polymer =1.28g / cm 3 ,ρ modifer =1.06g / cm 3 ). The film thickness was measured using a stylus step gauge (P-6, manufactured by KLA Tencor) from the uneven shape of a sample whose surface had been partially scraped. FIG. 4 shows photographs of the hybrid membranes of Experimental Examples 3-1, 3-4, and 3-5.
[0235] From Table 4, it was confirmed that the thin film made of a dispersion containing a carboxyl group-containing methyl-substituted PPS and surface-modified zirconia nanoparticles has excellent dispersibility, a high refractive index, and excellent transparency.
[0236] Example 4 <Sulfur-containing polymer 3> (Synthesis of Monomer) Chloroform (300 mL), m-toluenethiol (24.8 g, 0.2 mol) were added to a 1000 mL conical beaker, and then a methanol solution (300 mL) containing iodine (25.4 g, 0.1 mol) was added, followed by stirring at room temperature for 1 hour. Then, an aqueous sodium thiosulfate solution was added to remove the iodine, and the solvent was distilled off. The reaction solution was dispersed in diethyl ether, and the liquids were separated and washed in the order of an aqueous hydrochloric acid solution (3 mass%), an aqueous sodium hydroxide solution (5 mass%), and pure water, followed by dehydration, solvent removal, and vacuum drying to recover bis(3-methylphenyl)disulfide. The yield was 80%. 1 H-NMR, 13 The structure was confirmed by C-NMR and FAB-MS. [Bis(3-methylphenyl) disulfide] 1 H-NMR (CD2Cl2,500MHz,ppm):δ=7.30(s,2H,Ph-H),7.28(d,2H,Ph-H),7.16(t,2H,Ph-H),7.01 (d,2H,Ph-H),2.78(s,6H,methyl-H) 13 C-NMR(CD2Cl2,ppm):δ=139.5,137.1,129.2,128.4,128.3,124.9,21.4 Mass:m / z 245.7(found),246.4(calcd).
[0237] [ka]
[0238] (Polymer synthesis) In a 50mL three-neck flask, diphenyl disulfide (3.64g, 16.67mmol) and bis(3-methylphenyl) disulfide (0.821g, 3.33mmol) obtained in the above (synthesis of monomer) were added to a dichloromethane solution (20mL) of 2,3-dichloro-5,6-dicyano-parabenzoquinone (DDQ, 1M) and trifluoroacetic acid (1M), and oxidative polymerization was performed by stirring at room temperature for 20 hours. After removing the by-products in the polymerization solution with a glass filter, the polymerization solution was dropped into hydrochloric acid acidified methanol to precipitate the produced polymer, and the precipitate was collected as a powder by filtering with a glass filter. After that, it was washed with an aqueous potassium hydroxide solution (0.1M), pure water, and methanol in that order, and dried in vacuum to obtain a polymer A having a repeating unit represented by the following formula (A). 1 H-NMR, 13 Polymer A was identified by C-NMR. The weight average molecular weight Mw of the obtained polymer A was 2700, and Mn was 1300. The glass transition temperature was 73°C. The refractive index was 1.79. , S. The bond energy was 162-164 eV. In other words, S was 100% sulfide. The yield of polymer A was 72%. x in formula (A) was 0.833. [Polymer A] 1 H-NMR(CD2Cl2,500MHz,ppm):δ=7.23(m,23H,Ph-H),2.25(s,3H,methyl-H) 13 C-NMR(CD2Cl2,ppm):δ=141.2,136.5,134.1,131.1,127.9,127.4,20.7
[0239] [ka]
[0240] (Synthesis of thiol-terminated PPS) 8.92 g of polymer A was weighed out and dissolved in tetrahydrofuran (THF, 79.3 mL), then 0.6 g of sodium borohydride was added, and 16 mL of methanol was added dropwise while stirring, followed by stirring at 25°C for 18 hours. After the reaction was completed, the polymer was purified by precipitation in hydrochloric acid-acidified methanol (1600 ml, containing 5 vol% hydrochloric acid), filtered with a glass filter, and washed with methanol and water. After overnight vacuum drying (25°C, 12 hours), thiol-terminated methyl-substituted polyphenylsulfide resin (SH-MePPS) was obtained (yield 68%, terminal thiol concentration 100%).
[0241] (Synthesis of methyl-substituted PPS (P-MePPS) at the phosphate terminal) 6.1 g (53.9 mmol of monomer units) of the SH-MePPS obtained above was weighed out and dissolved in 53.9 mL of THF, and then 0.82 g (21.6 mmol) of sodium borohydride and 19 g (10.7 mmol) of 2-acryloyloxyethyl phosphate were added, and 1.6 mL of methanol was added dropwise while stirring, followed by stirring at 25°C for 18 hours. After the reaction was completed, the solution was precipitated and purified in hydrochloric acid-acidified methanol (1100 mL, containing 5 vol% hydrochloric acid), filtered with a glass filter, washed with methanol and water, and vacuum dried overnight (25°C, 12 hours), to obtain 5.7 g of methyl-substituted PPS (P-MePPS) with terminal phosphate groups (yield 94%, one phosphate group was introduced per 19.2 monomer units of terminal phosphate). NMR and GPC showed that the phosphoric acid introduction rate of thiol groups was 60%.
[0242] (Synthesis of oxidized PPS with methyl substituted phosphate terminals (P-MePPSO)) The P-MePPS (5.7 g, 50.7 mmol) obtained above was added to 203 mL of a chloroform solution of metachloroperbenzoic acid (mCPBA, 0.25 M), and the mixture was stirred at room temperature for 20 hours to cause oxidation. The reaction solution was then dropped into hydrochloric acid-acidified methanol, centrifuged, and vacuum dried to obtain a polymer P-MePPSO (sulfur-containing polymer 3). The yield was 95%. The structure of the obtained polymer is as follows: 1 The compound was identified by H-NMR, IR, and XPS. The elemental content ratio (O / S) of the oxygen atom bonded to the sulfur atom in the main chain and the sulfur atom in the main chain was 1.
[0243] (Preparation of Phosphate-Terminated Methyl-Substituted Oxidized PPS (P-MePPSO) and ZrO2 Particle Composite Composition) P-MePPSO was dissolved in 1,1,1,3,3,3-hexafluoro-2-propanol (HFIP) to a concentration of 5% by mass (solute mass / solution mass). In addition, P-MePPSO and a zirconia (ZrO2) nanoparticle-dispersed methyl ethyl ketone solution (Nippon Shokubai, ZP-153, solid content 70% by mass) were dissolved in HFIP to a concentration of 2.5% by mass (solute mass / solution mass) in terms of solid content. The solution was coated on a glass slide with a spin coater (500 rpm x 60 s, film thickness about 1 μm), dried at 260 ° C for 10 minutes to form a film, and the transmittance was evaluated. In addition, HFIP was added to each solution to dilute it 10 times, and the solution was coated on a silicon wafer with a spin coater (1000 rpm x 60 s, film thickness 10-900 nm), dried at 260 ° C for 10 minutes to form a film, and the refractive index was evaluated. The results are shown in Table 5.
[0244] Comparative Example 3 A zirconia nanoparticle dispersion was prepared, a film was formed, and its transmittance and refractive index were evaluated in the same manner as in Example 4, except that polymer A-1, which was obtained by oxidizing the main chain of polymer A, was used instead of P-MePPSO. The results are shown in Table 5. The preparation method of polymer A-1 is shown below.
[0245] (Preparation of Polymer A-1) In a 50 mL recovery flask, the polymer A (0.302 g) obtained above was added to 10 mL of a chloroform solution of metachloroperbenzoic acid (mCPBA, 0.25 M), and the mixture was stirred at room temperature for 20 hours to cause oxidation. The reaction solution was then dropped into hydrochloric acid-acidified methanol, centrifuged, and vacuum dried to obtain polymer A-1 having a repeating unit represented by the following formula (A-1). The yield was 97%. The structure of the obtained polymer is as follows: 1 The polymer was identified by H-NMR, IR, and XPS. The elemental content ratio (O / S) of the oxygen atom bonded to the sulfur atom in the main chain of the polymer to the sulfur atom in the main chain was 0.92 (0.92 / 1). S The binding energy peaks were observed at 165 eV and 163 eV, and the peaks could be separated into 164-168 eV (sulfoxide) and 162-168 eV (sulfide), with the peak areas of the sulfoxide and sulfide being 47.8:4.4. In the formula (A-1), x was 0.08 and y was 0.92. [Polymer A-1] 1 H-NMR(CD2Cl2,500MHz,ppm):δ=7.55(m,23H,Ph-H),2.34(s,3H,methyl-H) IR(cm -1 ):1045(νS=O)
[0246] [ka]
[0247] [Table 5]
[0248] From Table 5, it was confirmed that P-MePPSO has a high refractive index of 1.7 or more, and a high transmittance of 87% or more. It was also confirmed that P-MePPSO has a higher transmittance and refractive index when it is made into a composition with ZrO2 than when it is the polymer alone. It was found that the aggregation of ZrO2 can be suppressed even at a high temperature of 260°C, and that it is a highly heat-resistant, high-refractive-index, transparent material that is applicable to polymer injection molding. On the other hand, the transmittance of polymer A-1 in Comparative Example 3 was reduced when it was made into a composition with ZrO2.
[0249] Example 5 <Sulfur-containing polymer 4> (Synthesis of thiol-terminated PPS-2) 20 g (0.18 mol) of polymer A used in Example 4 above was weighed out and dissolved in tetrahydrofuran (THF, 200 mL), and then 4.8 g of triphenylphosphine was added and stirred at 35° C. for 18 hours. After the reaction was completed, the polymer was purified by precipitation in hydrochloric acid-acidified methanol (2000 mL, containing 5 vol% hydrochloric acid), filtered with a glass filter, and washed with methanol and water. After overnight vacuum drying (25° C., 12 hours), a thiol-terminated methyl-substituted polyphenylsulfide resin (SH-MePPS-2) was obtained (yield 91%, terminal thiol concentration 100%).
[0250] (Synthesis of methyl-substituted PPS at the carboxyl end (COOH-MePPS)) 1 g of the above SH-MePPS-2 was weighed out and dissolved in 10 mL of THF and 0.5 mL of water, after which 0.28 g of 2-carboxyethyl acrylate and 0.76 g of potassium carbonate were added and stirred for 18 hours at 25° C. After the reaction was completed, the solution was precipitated and purified using hydrochloric acid-acidified methanol (100 mL, containing 5 vol% hydrochloric acid), filtered through a glass filter, washed with methanol and water, and vacuum dried overnight (25° C., 12 hours), to obtain 0.8 g of methyl-substituted PPS (COOH-MePPS) with terminal carboxyl groups (yield 81%, terminal carboxylic acid was introduced at one carboxylic acid group per 22.3 monomer units). 1 H-NMR and GPC revealed that the introduction rate of thiol groups to carboxylic acid was 52%.
[0251] (Synthesis of oxidized PPS with methyl-substituted carboxyl end groups (COOH-MePPSO)) 0.8 g of the COOH-MePPS obtained above was added to 28.5 mL of a chloroform solution of metachloroperbenzoic acid (mCPBA, 0.25 M), and the mixture was stirred for 20 hours at 25°C for oxidation. The reaction solution was then dropped into hydrochloric acid-acidified methanol, centrifuged, and vacuum dried to obtain a polymer COOH-MePPSO (sulfur-containing polymer 4). The yield was 85%. The structure of the obtained polymer is as follows: 1 The polymer was identified by H-NMR, IR, and XPS. The elemental content ratio (O / S) of the oxygen atom bonded to the sulfur atom in the main chain of the polymer to the sulfur atom in the main chain was 0.97.
[0252] (Preparation of a composite composition of carboxyl-terminated methyl-substituted oxidized PPS (COOH-MePPSO) and ZrO2 particles) The above-mentioned COOH-MePPSO and a zirconia nanoparticle-dispersed methyl ethyl ketone solution (ZP-153, Nippon Shokubai Co., Ltd., solid content 70% by mass) were dissolved in HFIP to a solid content of 2.5% by mass (solute mass / solution mass) to prepare a composite composition (sulfur-containing polymer composition). Furthermore, a composition was prepared by dissolving the above-mentioned COOH-MePPSO in 1,1,1,3,3,3-hexafluoro-2-propanol (HFIP) so that the COOH-MePPSO concentration was 5% by mass (solute mass / solution mass). Each of the compositions was applied to a slide glass by a spin coater (500 rpm×60 s, film thickness about 1 μm), and dried by heating at 260° C. for 10 minutes to form a film, and the transmittance was evaluated. In addition, each composition was further diluted 10-fold by adding HFIP, and then coated onto a silicon wafer with a spin coater (1000 rpm x 60 s, film thickness 10-900 nm), and dried by heating at 260°C for 10 minutes to form a film, and the refractive index was evaluated. The results were also compared with the polymer A-1 of Comparative Example 3 and a composite composition of the polymer A-1 and a zirconia nanoparticle dispersion. The results are shown in Table 6.
[0253] [Table 6]
[0254] From Table 6, it was confirmed that the oxidized PPS with methyl-substituted carboxyl terminals has a high refractive index of 1.7 or more and a high transmittance of 86% or more. It was also confirmed that the transmittance and refractive index of the oxidized PPS with methyl-substituted carboxyl terminals is higher when it is combined with ZrO2 than when it is the polymer alone. It was also found that the aggregation of ZrO2 can be suppressed even at a high temperature of 260°C, making it a heat-resistant, high-refractive index, transparent material that can be used for polymer injection molding.
[0255] Example 6 <Sulfur-containing polymer 5> (Synthesis of vinyl-terminated methyl-substituted PPS (V-MePPS)) 1 g of the above SH-MePPS-2 was weighed out and dissolved in 20 mL of THF and 1 mL of water, and then 0.34 g of VEEA (registered trademark) (manufactured by Nippon Shokubai, CAS86273-46-3) and 0.76 g of potassium carbonate were added and stirred at 25°C for 18 hours. After the reaction was completed, the solution was precipitated and purified in hydrochloric acid acidified methanol (200 mL, containing 5 vol% hydrochloric acid), filtered through a glass filter, washed with methanol and water, and vacuum dried overnight (25°C, 12 hours), to obtain 0.9 g of vinyl-terminated methyl-substituted PPS (V-MePPS) (sulfur-containing polymer 5) (yield 94%, terminal vinyl group was introduced at one vinyl group per 55.2 monomer units). NMR and GPC showed that the vinyl group introduction rate of the thiol group was 21%. Refractive index (n D ) was 1.73.
[0256] Example 7 <Sulfur-containing polymer 6> (Synthesis of Bromo-Containing Polymer B) Poly(2,6-dimethyl-1,4-phenylene sulfide) (PMPS) was synthesized in the same manner as in Example 1 (Synthesis of OMePPS), except that 2,6-dimethylthiophenol was used instead of 2-methoxybenzenethiol and bis(2,6-methylphenyl) disulfide was used instead of bis(2-methoxyphenyl) disulfide. The above PMPS (2.7242 g, repeating unit 20 mmol, 20 mmol) was added to a 300 mL three-neck flask and dissolved in chlorobenzene (100 mL). Next, NBS (N-bromosuccinimide, 3.5998g, 20mmol, 1eq. for PMPS) and AIBN (2,2'-azobisisobutyronitrile, 98.526mg, 0.6mmol, 0.03eq. for PMPS) were added, and nitrogen was bubbled at room temperature for 30 minutes. Then, the temperature was raised to 80°C, and the mixture was refluxed under a nitrogen atmosphere for 5 hours. After the reaction was completed, the mixture was cooled in an ice bath, and precipitates derived from NBS appeared, so they were filtered off. The collected filtrate was then concentrated using an evaporator, and then dropped into hydrochloric acid-acidified methanol (MeOH 800mL / HClaq.5vol%) for precipitation purification. The precipitate was collected by centrifugation, and after drying under reduced pressure, polymer B was obtained as a pale yellow powder (yield: 89%).
[0257] (Oxidation reaction of polymer main chain) Polymer B (0.98481 g, 5.0 mmol, 0.25 M) was added to a 50 mL flask and dissolved in chloroform (20 mL). Then, 1 equivalent of metachloroperbenzoic acid (mCPBA) was added and reacted at room temperature under air for 20 hours. After the reaction was completed, chloroform was added to the reaction solution, the precipitate was dispersed, and the precipitate was dropped into hydrochloric acid acidic methanol (MeOH 600 mL / HCl aq. 5 vol%) for precipitation purification. The precipitate was collected by centrifugation and dried under reduced pressure to obtain polymer B-1 as a white powder (yield: 77%, calculated assuming the reaction rate of mCPBA is 100%).
[0258] (Synthesis of Hydroxy Group-Containing Polymer B-1-1) Polymer B-1 (0.42003 g, 2.0 mmol, 0.2 M) was added to a 50 mL flask and dissolved in NMP (N-methyl-2-pyrrolidone, 10 mL). Then, H2O (1 mL, 10 vol% for NMP) was added and heated to reflux at 100°C for 90 hours. After the reaction was completed, the reaction solution was dropped into hydrochloric acid acidic methanol (MeOH 500 mL / HCl aq. 5 vol%) to perform precipitation purification. The precipitate was collected by centrifugation and dried under reduced pressure to obtain polymer B-1-1 (sulfur-containing polymer 6) as a light brown to grayish white powder (yield: 78%, calculated assuming that 100% of the bromo group was replaced with a hydroxy group).
[0259] The amount of SO and SO2 in each polymer was measured by IR, and the amount of OH, Br, and CH3 was measured by 1 It was determined by H-NMR. In addition, the glass transition temperature (Tg) and the refractive index (n D ), Abbe number (v D ) were evaluated by the method described above. The results are shown in Table 7.
[0260] [Table 7]
[0261] Experimental Examples 8-1 to 8-4 (Hybridization of Hydroxy Group-Containing Polymer B-1-1 with TiO2) In a 10 mL sample bottle, polymer B-1-1 (20 mg, 0.03 M) was dissolved in DMAc (dimethylacetamide, 4 mL), and hydrochloric acid ([HCl] / [Ti]=2) was added and stirred for 30 minutes. Next, a butanol solution of tetrabutyl orthotitanate (1.47 M Ti solution) was added to polymer B-1-1 in the mass composition shown in Table 8, and the mixture was stirred for another 30 minutes to prepare a hybrid solution (sulfur-containing polymer composition).
[0262] The obtained hybrid solution was drop cast onto a glass substrate or spin coated onto a silicon wafer to form a film with the thickness shown in Table 8, and then dried under reduced pressure at 60°C for 2 hours and at 150°C for 1 hour to produce a hybrid film. The absorbance at 400 nm and the refractive index (n D ), Abbe number (v D ) were evaluated by the method described above. The results are shown in Table 8. 5 shows measurement data of the refractive index of the sulfur-containing polymer compositions of Experimental Examples 8-1 and 8-4 in Example 7. In the figure, the solid line shows Experimental Example 8-1, and the dashed line shows Experimental Example 8-4. FIG. 6 shows photographs of the hybrid membranes obtained in Experimental Examples 8-1 to 8-4 in Example 7.
[0263] [Table 8]
[0264] From Table 8, it was confirmed that the sulfur-containing polymer composition containing the sulfur-containing polymer and metal oxide of the example had a high refractive index and high transparency.
[0265] Example 8 <Sulfur-containing polymer 7> (Synthesis of Bromo-Substituted PPS) Poly(2,6-dimethyl-1,4-phenylene sulfide) (PMPS) (1.5 g, repeat unit 11.0 mmol, 1 eq) was dissolved in chlorobenzene (55 mL) in a 100 mL two-neck flask. N-bromosuccinimide (NBS) (0.55 eq or 0.28 eq) and AIBN (0.016 eq or 0.008 eq) were then added and the mixture was heated to reflux at 135°C for 4 hours. After the reaction, the precipitated succinimide was filtered, and the filtrate was precipitated and purified in hydrochloric acid-acidified methanol (1000 mL, containing 5 vol% hydrochloric acid), filtered through a glass filter, washed with methanol and water, and dried in vacuum to obtain bromo-substituted PPS.
[0266] (Synthesis of vinyl-substituted PPS) Bromo-substituted PPS (0.5 g, 1 eq) was added to a 100 mL flask at each introduction ratio, and THF was added to make the polymer concentration 0.1 M. After dissolution, triphenylphosphine (4 eq relative to benzyl bromide) was added, and the mixture was heated to reflux at 70°C for 24 hours. After the reaction was completed, the solution was cooled, 37 mass% formaldehyde aqueous solution (32 eq relative to benzyl bromide) was added, and the mixture was stirred for 10 minutes, followed by potassium t-butoxide (4.2 eq relative to benzyl bromide), and the mixture was reacted at room temperature for 1 hour. After the reaction was completed, the vinyl-substituted PPS (sulfur-containing polymer 7) was obtained through precipitation purification in hydrochloric acid-acidified methanol (500 mL, containing 5 vol% hydrochloric acid), washing with methanol and water, and vacuum drying. The synthetic reaction formula for vinyl-substituted PPS is shown below.
[0267] [ka]
[0268] Table 9 shows the introduction ratio (x, y) of each structural unit in the obtained polymer and the glass transition temperature (Tg). Polymer 5 in Table 9 is polymer (5) in the above reaction formula, and polymer 6 is polymer (6) in the above reaction formula. The introduction ratios x and y are the values of x and y in the above reaction formula (6). Table 10 shows the polymer 6 obtained. 1 The H-NMR measurement results and various molecular weights are shown.
[0269] [Table 9]
[0270] [Table 10]
[0271] 1 In the above reaction formula (5), a methylene-derived peak was observed at 4.6 ppm by H-NMR, while in the above reaction formula (6), the peaks derived from the methylene group were reduced and new vinyl group-derived peaks were observed at 7.2, 5.4, and 5.2 ppm, confirming the structure. From IR, (5) is 1210 cm -1 In (6), the intensity of the C-Br stretching vibration is decreased and a new absorption at 910 cm -1 The CH out-of-plane bending vibration absorption of the vinyl group was observed, confirming the progress of the reaction. DSC showed that the glass transition temperature increased to a maximum of 201°C through bromination and vinylation.
[0272] The obtained sulfur-containing polymer had a refractive index of 1.7 or more, a Tg of 200°C or more, and was reactive.
[0273] Example 9 <Sulfur-containing polymer 8> (Synthesis of bis(2,6-dimethoxyphenyl)disulfide) Magnesium (1.16 g, 48 mmol) was added to a 100 mL two-neck flask and dispersed in THF (20 mL). After adding two drops of 1,2-dibromoethane and replacing with nitrogen, a THF solution of 1,3-dimethoxy-2-bromobenzene (8.68 g, 40 mmol / 10 mL) was added dropwise and reacted under reflux for 2 hours. After cooling to 0°C, sulfur (0.70 g, 22 mmol) was added and reacted at room temperature for another 3 hours. The mixture was quenched with dilute hydrochloric acid (10 vol%, 50 mL) and extracted with chloroform (150 mL). The solvent was removed using an evaporator to obtain a crude product of 3,5-dimethoxybenzenethiol. Furthermore, the crude product of 3,5-dimethoxybenzenethiol was dissolved in chloroform, and then an iodine-methanol solution (0.5 mM, 15 mL) was added dropwise and reacted for 1 hour. Unreacted iodine was reacted with an aqueous sodium thiosulfate solution (15 mass%), and the solvent was removed by an evaporator. The product was purified by separation (chloroform) and recrystallization (chloroform / methanol = 1:10), and bis(2,6-dimethoxyphenyl) disulfide (2,6-DMDPS) was obtained as a yellowish-white solid (yield 63%). FAB-MS (338.44 (m / z)), 1 H-NMR (7.22ppm(t,J=8.5Hz,2H),6.50ppm(d,J=9.0Hz,4H),3.69ppm(s,12H,Me)), 13 The structure was identified by C-NMR (161.2 ppm, 130.9 ppm, 113.0 ppm, 103.8 ppm, 56.0 ppm). The melting point was determined by DSC to be 205°C. The synthesis reaction formula is shown below.
[0274] [ka]
[0275] (Synthesis of dimethoxy-substituted PPS by oxidative polymerization) The above 2,6-DMDPS (0.17 g, 0.5 mmol) was added to a 10 mL flask and dissolved in 1,2-dichloroethane (1 mL, DCE). Trifluoroacetic acid (TFA) (7.5 μL, 0.1 M) was then added, and DDQ (0.11 g, 1 eq of 2,6-DMDPS) was added as an oxidizing agent and reacted at room temperature. After the reaction was completed, DCE (2 mL) was added to disperse the product, which was then filtered through a glass filter. The filtrate was dropped into hydrochloric acid-acidified ethanol (5 vol%, 300 mL) for precipitation purification, and collected through a glass filter. The product was washed with an aqueous potassium hydroxide solution (5 mass%), pure water, and methanol, and dried under reduced pressure to obtain a dimethoxy-substituted PPS (sulfur-containing polymer 8) as a white powder (yield 72%, Mn 3300, Mw 4100, Mw / Mn = 1.2). IR measurement revealed that the m-substitution for sulfide (870 cm -1 ), p-substituted product (910cm -1 ) and observed the absorption of the CH out-of-plane bending vibration of each aromatic ring. 1 The ratio of each substituent was calculated by H-NMR measurement, and it was found that (m-substitution):(p-substitution):(branched structure)=x:y:z=0.34:0.55:0.11. 13 C, 13 The corresponding peaks were also identified by C-DEPT NMR. The reaction formula for the oxidative polymerization of 2,6-DMDPS and the chemical formula for the resulting dimethoxy-substituted PPS (P1) are shown below.
[0276] [ka]
[0277] In the X-ray diffraction (XRD) profile of dimethoxy-substituted PPS (P1), no crystalline peaks were observed, indicating that it was amorphous. In addition, the 5% weight loss temperature measured by thermogravimetry (TGA) was 334°C, and the glass transition temperature measured by DSC was 116°C.
[0278] Dimethoxy-substituted PPS (P1) was dissolved in 1,1,2,2-tetrachloroethane at a concentration of 30 mg / mL, drop-cast onto a glass substrate, and dried under reduced pressure at 40°C for 4 hours to form a film. The film had a thickness of 5.2 μm, and the transmittance at 400 nm of this film was 82%. In addition, a DMF solution (concentration: 30 mg / mL) of dimethoxy-substituted PPS (P1) was spin-coated onto a silicon wafer to form a film, and the refractive index and Abbe number were measured, showing n D =1.74,v D =16. FIG. 7 shows the XRD profiles of polyphenylsulfide resin (PPS) and dimethoxy-substituted PPS (P1) membranes. FIG. 8 shows the measurement data of the transmittance of the dimethoxy-substituted PPS (P1) film by UV-vis measurement, and FIG. 9 shows the measurement data of the refractive index of the dimethoxy-substituted PPS film (P1).
[0279] (Synthesis of dihydroxy-substituted PPS) The dimethoxy-substituted PPS (P1) obtained above (0.2 g, 2.4 mmol of -OMe) was added to a 50 mL flask and dissolved in dichloromethane (DCM) (10 mL) under an argon atmosphere in a glove box. The mixture was cooled to 0°C, and 1 M boron tribromide dichloromethane solution (6 mL) was added using a syringe. The mixture was reacted at 0°C for 30 minutes and at room temperature for 20 hours. The mixture was quenched with water and the solvent was removed using an evaporator. The mixture was redissolved in methanol and purified by precipitation into water. The precipitate was collected using a glass filter and dried under reduced pressure to obtain dihydroxy-substituted PPS (P2) (sulfur-containing polymer 8) (yield 77%). The reaction formula is shown below.
[0280] [ka]
[0281] 1 1H-NMR measurements confirmed the introduction of hydroxy groups by demethylation, and the introduction rate was calculated to be 94%. 1 H-NMR measurement showed that the hydroxyl group peak disappeared, indicating that it has proton exchange properties. IR measurement of dihydroxy-substituted PPS (P2) showed the absorption of hydrogen-bonded OH stretching vibration (3400 cm -1 ) was observed, confirming the progress of the reaction. In the XRD measurement of dihydroxy-substituted PPS (P2), no crystalline peaks derived from PPS were observed, indicating that the amorphous nature was maintained even after demethylation. The glass transition temperature of dihydroxy-substituted PPS (P2) was 140°C, which was significantly higher than that of dimethoxy-substituted PPS (P1) due to the introduction of hydrogen bonds. Figure 10 shows the XRD profiles of polyphenylsulfide resin (PPS) and dihydroxy-substituted PPS (P2). Figure 11 shows the DSC curves of dimethoxy-substituted PPS (P1) and dihydroxy-substituted PPS (P2). That is, P1 is PPS before demethylation, and P2 is PPS after demethylation.
[0282] In addition, dihydroxy-substituted PPS (P2) was dissolved in DMF at a concentration of 15 mg / mL, drop-cast onto a glass substrate, and dried under reduced pressure at 40°C for 4 hours to form a film. The film had a thickness of 2.5 μm, and the transmittance of this film at 400 nm was 90%. In addition, a DMF solution of dihydroxy-substituted PPS (P2) (concentration: 30 mg / mL) was spin-coated onto a silicon wafer to form a film, and the refractive index and Abbe number were measured, showing that n D =1.85,v D =16. FIG. 12 shows the measurement data of the transmittance of the hydroxy-substituted PPS (P2) film by UV-vis measurement, and FIG. 13 shows the measurement data of the refractive index of the hydroxy-substituted PPS (P2) film.
[0283] The true densities of dimethoxy-substituted PPS (P1) and hydroxy-substituted PPS (P2) were measured using a dry-type automatic density meter (AccuPycII 1340, Shimadzu Corporation), and were found to be 1.42 g / cm. 3 , 1.87g / cm 3 From the above, it is considered that the interaction between the main chains is increased by the intermolecular hydrogen bonds formed by the hydroxyl groups in the side chains of the hydroxy-substituted PPS (P2), and the increased density and reduced molecular volume contributed to the improvement of the refractive index.
[0284] Example 10 Crosslinking of vinyl-substituted PPS to impart toughness Three types of vinyl-substituted PPS (P3) were synthesized in the same manner as in Example 8, except that poly(3-methyl-1,4-phenylene sulfide) was used instead of poly(2,6-dimethyl-1,4-phenylene sulfide). Each vinyl-substituted PPS (P3) was dissolved in 1,1,2,2-tetrachloroethane, passed through a membrane filter, and then m-benzenedithiol was added and stirred to prepare a sulfur-containing polymer composition. That is, the concentration of P3 was adjusted to 100 mg / mL, and 0.5 equivalents of m-benzenedithiol were added relative to the vinyl group. 1.5 mL of the sulfur-containing polymer composition was dropped onto a 1 cm x 5 cm Teflon (registered trademark) plate and heated at 50 ° C for 12 hours, 100 ° C for 2 hours, 120 ° C for 12 hours, and 150 ° C for 3 hours to obtain a crosslinked film P3-BDTH (crosslinked body). The chemical formula showing the crosslinking reaction is shown below. Table 11 shows the vinyl group (CH = CH2) content and Br content of each of the vinyl-substituted PPS used, and the results of the thermal properties and dynamic viscoelasticity measurements of the obtained crosslinked body. In Table 11, CH=CH2 (mol%) and Br (mol%) are 1 Measured by H-NMR. a) was determined by DSC measurement. b) , G', G'', and tan δ were determined by dynamic mechanical analysis (DMA).
[0285] [ka]
[0286] [Table 11]
[0287] As can be seen from Table 11, the crosslinked bodies 1, 2 and 3 prepared were all bendable and flexible. Furthermore, when these crosslinked bodies were subjected to dynamic viscoelasticity measurement, the storage modulus of Crosslinked Body 2 showed a maximum value G′=1.90 GPa.
[0288] Example 11 <Sulfur-containing polymer 9> (Synthesis of methyl-terminated methoxy-substituted PPS (Me-OMePPS)) In a 100mL two-neck flask, 0.6g of methoxy-substituted PPS (OMePPS) (Mn=2500, disulfide concentration 0.24mmol) was dissolved in THF (8.1mL), cooled to 0℃, and iodomethane (299μL, 4.8mmol, 20eq) was added and stirred. When the solution became homogeneous, a solution of sodium borohydride (182mg, 4.8mmol, 20eq) dispersed in water (0.9mL) was added dropwise. After foaming was completed, the temperature was raised to room temperature and the reaction was carried out for 3 hours. The solution after the reaction was precipitated and purified in methanol (300mL), recovered with a glass filter, washed with methanol and water, and dried under reduced pressure to obtain methyl-terminated methoxy-substituted PPS (Me-OMePPS) as a white powder (0.47g, 79% yield) (GPC (THF, polystyrene standard): Mn=2100, Mw / Mn=1.8). 1 From H-NMR, a new peak derived from the terminal methyl group appeared around 2.4 to 2.1 ppm, and the number average molecular weight Mn calculated from the integral ratio of the peak derived from the methoxy group (4 to 3.3 ppm) and the peak derived from the terminal methyl group was 2100. The calculation used was Mn = 138.2 (molecular weight of repeating unit) × AOMe (integral value of the peak derived from the methoxy group) / AMe (integral value of the peak derived from the terminal methyl group). 1 H-DOSY-NMR revealed peaks attributable to methoxy and methyl groups on the same diffusion coefficient, confirming the addition of methyl groups to the main chain ends.
[0289] [ka]
[0290] (Synthesis of Hydroxy-Substituted PPS (OHPPS)) 0.3 g of the above Me-OMePPS was added to a 100 mL flask, and after being carried into a glove box, it was dissolved in dichloromethane (9.1 mL). The flask was sealed and then carried out, cooled to 0°C, and 1 M boron tribromide dichloromethane solution (5.42 mL, 5.42 mmol) was added using a syringe, stirred at 0°C for 30 minutes, then warmed to room temperature, and stirred for another 20 hours. After the reaction was completed, the flask was cooled in an ice bath while quenching by slowly dropping pure water (12 mL) and removing the solvent with an evaporator. The remaining product was redissolved in DMF (10 mL) and precipitated and purified in 1 M hydrochloric acid (300 mL), obtaining a white precipitate. After recovery with a glass filter and washing with water, the recovered solid was vacuum dried until it was completely dry. The product was redissolved in acetone (20 mL), and then purified by reprecipitation in 1 M hydrochloric acid (200 mL) (twice in total). The product was then recovered on a glass filter, washed with water, and dried in vacuum to obtain hydroxy-substituted PPS (OHPPS) (sulfur-containing polymer 9) as a white powder (0.21 g, yield 79%) (Mn (calculated by NMR) = 2000). 1 In H-NMR, the peaks derived from methoxy groups (4-3.3 ppm) disappeared after demethylation, and a broad peak derived from hydroxyl groups was observed at 11-9.5 ppm, confirming the progress of the reaction. The peak integral ratio derived from hydroxyl groups and aromatic rings was 1:1, so the introduction rate of hydroxyl groups was calculated to be 100%. IR showed that after the reaction, the OH stretching vibration (3400 cm -1 ) absorption was observed, and the COC stretching vibration (1200 cm) observed before the reaction was observed. -1 ) absorption due to the CH stretching vibration of the methyl group disappeared, which supported the progress of the reaction. -1 ) was significantly attenuated after the reaction, and the Ar-H stretching vibration (3070 cm -1 ), CH out-of-plane bending vibration (920~800cm -1 ) absorption was observed even after the reaction, which supported the structure. No crystalline peaks were observed in the XRD profiles of Me-OMePPS and OHPPS even after demethylation. The average distance between aromatic rings calculated from the Bragg equation was 4.5 Å for Me-OMePPS and 4.2 Å for OHPPS (CuKα radiation: 1.54 Å used). DSC showed that the glass transition temperature of Me-OMePPS was 119°C, while that of OHPPS was increased to 125°C, suggesting that the interaction between molecular chains was strengthened by intermolecular hydrogen bonds.
[0291] [ka]
[0292] Hydroxy-substituted PPS (OHPPS) was dissolved in DMF at a concentration of 15 mg / mL, drop-cast onto a glass substrate, and dried under reduced pressure at 50°C for 12 hours and at room temperature for 12 hours to obtain a colorless, transparent thin film with a thickness of 4.5 μm. Also, methyl-terminated methoxy-substituted PPS (Me-OMePPS) was dissolved in N,N-dimethylacetamide (DMAc) at a concentration of 15 mg / mL, drop-cast onto a glass substrate, and dried under reduced pressure at 50°C for 12 hours and at room temperature for 12 hours to obtain a colorless, transparent thin film with a thickness of 2.8 μm. The transmittance of the two thin films obtained was calculated based on a thickness of 1 μm. Figure 14 shows the measurement data of the transmittance of these thin films (converted to a thickness of 1 μm). As shown in Figure 14, the transmittance of OHPPS was 97%, which was confirmed to be higher than the transmittance of Me-OMePPS, which is 93%.
[0293] In addition, OHPPS (60 mg) was dissolved in DMF (1 mL) and dropped onto a silicon wafer, and the wafer was rotated at 2000 rpm for 30 seconds using a spin coater to form a film. The obtained sample was dried under reduced pressure at 50°C for 12 hours and at room temperature for 12 hours to obtain a uniform thin film. Me-OMePPS (30 mg) was dissolved in 1,1,2,2-tetrachloroethane (1 mL) and dropped onto a silicon wafer, and the wafer was rotated at 500 rpm for 45 seconds and at 1500 rpm for 50 seconds using a spin coater to form a film. The obtained sample was dried under reduced pressure at 50°C for 12 hours and then at room temperature for 12 hours to obtain a uniform thin film. The refractive index (D line) and Abbe number of the obtained thin film were measured. The refractive index measurement data are shown in FIG. 15. The measurement results are shown in Table 12. From Table 12, it was confirmed that OHPPS having a hydroxyl group has a higher refractive index and a smaller Abbe number than Me-OMePPS.
[0294] The true densities of Me-OMePPS and OHPPS were measured using a dry automatic density meter (AccuPycII 1340, Shimadzu Corporation). The measurement results are shown in Table 12. Table 12 shows that OHPPS has a higher true density than Me-OMePPS, which suggests that the intermolecular hydrogen bonds formed by the hydroxyl groups on the OHPPS side chains increase the interactions between the main chains, and that the increased density and reduced molecular volume contributed to the improvement of the refractive index.
[0295] [Table 12] < / ir>
Claims
1. A polymer having at least one structural unit selected from the group consisting of a structural unit (A) represented by the following general formula (1), a structural unit (B) represented by the following general formula (2), and a structural unit (C) represented by the following general formula (3): The polymer has a reactive functional group, the elemental ratio (O / S) of oxygen atoms O bonded to sulfur atoms S in the main chain to sulfur atoms S in the main chain, as determined using an X-ray photoelectron spectrometer, is 0.1 to 1.5; The reactive functional group is an acidic functional group, a basic functional group, a curable functional group, a nitro group, a nitroso group, or a group containing these functional groups. A sulfur-containing polymer. 【Chemistry 1】 【Chemistry 2】 【Chemistry 3】 (In the formulas (1), (2) and (3), X 1 , X 2 and X 3 are the same or different and each represents a divalent aromatic hydrocarbon group which may have a substituent.
2. The sulfur-containing polymer according to claim 1, characterized in that it contains at least one structural unit selected from the group consisting of the structural unit (A), the structural unit (B), and the structural unit (C) as a repeating unit. ...
3. The sulfur-containing polymer according to claim 1 or 2, wherein the sulfur-containing polymer has the reactive functional group at a main chain end and / or a side chain.
4. The sulfur-containing polymer according to any one of claims 1 to 3, characterized in that the reactive functional group is at least one functional group selected from the group consisting of a carboxyl group, a phosphoric acid group, a phosphonic acid group, a hydroxyl group, and a curable functional group, or a group containing the functional group.
5. The substituent is a reactive functional group, a halogen atom, or an alkyl group, an alkoxy group, an aryl group, an aralkyl group, or a sulfur-containing substituent, which may have a substituent. The sulfur-containing polymer according to any one of claims 1 to 4.
6. The sulfur-containing polymer according to any one of claims 1 to 5, which is for optical use.
7. A sulfur-containing polymer composition comprising the sulfur-containing polymer according to any one of claims 1 to 6, and at least one selected from the group consisting of an inorganic substance, a crosslinking agent, and an organic resin.
8. A cured product of the sulfur-containing polymer according to any one of claims 1 to 6.
9. A cured product of the sulfur-containing polymer composition according to claim 7.
10. A method for producing a sulfur-containing polymer according to any one of claims 1 to 6, The process includes a step of reacting a sulfur-containing aromatic polymer having a disulfide bond and / or a thiol group at its terminal with a compound having a polymerizable double bond and a reactive functional group. A method for producing a sulfur-containing polymer, comprising the steps of:
Citation Information
Patent Citations
Novel heat-resistant resin composition
JP1990080458A
Sulfur-containing acrylic oligomer composition
JP1992169568A
Functional group terminated polysulfide compound and its production
JP1997059382A
Novel polythioether having hydroxymethyl groups as side chains and its production
JP1998306162A
Polyelectrolyte and ion exchanger
JP2000080166A